Resin composition, method for producing resin composition, and molded article

By using a resin composition with a core-shell structure in a polar resin, combined with the compatible agent of the thermoplastic resin, the compatibility problem between the hydrogenated block copolymer and the polar resin is solved, and a resin composition with high shock absorption, good moldability and impact resistance is achieved.

CN113825775BActive Publication Date: 2025-04-04KURARAY CO LTD
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
CN202080037872.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-27
Filing Date
2020-05-22
Publication Date
2025-04-04
Estimated Expiration
2040-05-22

AI Technical Summary

Technical Problem

When hydrogenated block copolymer is added to polar resins such as polyamide resins, the processability, moldability, mechanical properties, etc. are easily reduced due to the low compatibility of hydrogenated block copolymers to polar resins. The prior art mainly focuses on improving impact resistance rather than shock absorption.

Method used

A resin composition including a thermoplastic resin (A), a thermoplastic resin (B) and a polar resin (C) is used to form a core-shell structure by using a thermoplastic resin (B) as a compatible agent to improve the dispersion of the thermoplastic resin (A) in the polar resin (C), thereby improving the shock absorption, moldability and impact resistance of the resin composition.

Benefits of technology

It is achieved to show high shock absorption, good moldability and excellent impact resistance at higher temperatures, and solves the problems of compatibility and performance reduction in the prior art.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113825775B_ABST
    Figure CN113825775B_ABST
Patent Text Reader

Abstract

Provided are resin compositions that exhibit high shock absorption, good moldability, and excellent impact resistance even at relatively high temperatures. A resin composition comprising a thermoplastic resin (A), a thermoplastic resin (B), and a polar resin (C), wherein the resin composition satisfies the following conditions (1) to (3): (1) the thermoplastic resin (B) has at least one of a reactive functional group and a monomer unit containing a heteroatom; (2) the thermoplastic resin (A) and the thermoplastic resin (B) are different types of resins; and (3) relative to the total mass of the resin composition, the content of the thermoplastic resin (A) is 1 to 30% by mass, the content of the thermoplastic resin (B) is 1 to 30% by mass, and the content of the polar resin (C) is 40 to 98% by mass.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a resin composition, a method for producing the resin composition, and a molded article. Background Art

[0002] Block copolymers having a polymer block containing a structural unit derived from an aromatic vinyl compound and a polymer block containing a structural unit derived from a conjugated diene compound and their hydrides are known to have shock-absorbing properties and are used in shock-absorbing materials. In addition, the block copolymers and their hydrides may have properties such as sound insulation, heat resistance, impact resistance, and adhesion in addition to shock-absorbing properties, and are believed to be useful in a variety of applications.

[0003] For example, in order to improve mechanical properties such as shock absorption, flexibility, heat resistance, tensile strength and impact resistance, hydrogenated block copolymers of styrene compounds and conjugated diene compounds such as isoprene and butadiene having specific tan δ peak temperatures and vinyl bond amounts have been disclosed (for example, see Patent Documents 1 to 4).

[0004] Furthermore, by adding the above-mentioned hydrogenated block copolymer to, for example, a polyamide resin, the vibration damping property of the polyamide resin can be improved.

[0005] In addition, Patent Document 5 describes that a mixed resin obtained by melt-mixing a polyamide resin and a compatibilizer is melt-mixed with a polyolefin resin.

[0006] Patent Document 6 describes a modifier that is blended into a polyolefin resin to improve the impact resistance of a molded product. The modifier is described as comprising a dispersed phase dispersed in a continuous phase of a polyolefin resin, and the dispersed phase comprises a polyamide resin and a modified elastomer.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2002-284830

[0010] Patent Document 2: International Publication No. 2000 / 015680

[0011] Patent Document 3: Japanese Patent Application Publication No. 2006-117879

[0012] Patent Document 4: Japanese Patent Application Publication No. 2010-053319

[0013] Patent Document 5: Japanese Patent Application Publication No. 2013-147648

[0014] Patent document 6: International Publication No. 2017 / 094738. Summary of the invention

[0015] Problems to be solved by the invention

[0016] When the hydrogenated block copolymer is added to a polar resin such as a polyamide resin, the polar resin to which the hydrogenated block copolymer is added has a problem that processability, moldability, mechanical properties, etc. are easily reduced due to the low compatibility of the hydrogenated block copolymer with the polar resin.

[0017] The above-mentioned patent documents 5 and 6 are technologies intended to improve the compatibility of polyamide resins and polyolefin resins. However, the technologies described in the two documents are mainly aimed at improving impact resistance, and no research has been conducted on improving shock absorption, so they do not have sufficient shock absorption. In order to have impact resistance, shock absorption and moldability, further improvement is required.

[0018] Therefore, an object of the present invention is to provide a resin composition which exhibits high vibration damping properties even at relatively high temperatures, has good moldability, and is excellent in impact resistance.

[0019] Means for solving problems

[0020] As a result of intensive studies to solve the above-mentioned problems, the present inventors have conceived the present invention described below and have found that the problems can be solved.

[0021] That is, the present invention is as follows.

[0022] [1] A resin composition comprising a thermoplastic resin (A), a thermoplastic resin (B), and a polar resin (C), wherein the resin composition satisfies the following conditions (1) to (3),

[0023] (1) The thermoplastic resin (B) has at least one of a reactive functional group and a monomer unit containing a heteroatom;

[0024] (2) The thermoplastic resin (A) and the thermoplastic resin (B) are different types of resins;

[0025] (3) With respect to the total mass of the resin composition, the content of the thermoplastic resin (A) is 1 to 30 mass %, the content of the thermoplastic resin (B) is 1 to 30 mass %, and the content of the polar resin (C) is 40 to 98 mass %.

[0026] [2] An automobile component comprising the above-mentioned resin composition.

[0027] [3] A molded article of a resin composition comprising a thermoplastic resin (A), a thermoplastic resin (B), and a polar resin (C),

[0028] The resin composition satisfies the above conditions (1) to (3),

[0029] In the above-mentioned molded product, there is a core-shell structure, in which the thermoplastic resin (A) and the thermoplastic resin (B) are dispersed in the polar resin (C), and the dispersion diameter D(A) of the thermoplastic resin (A) and the dispersion diameter D(B) of the thermoplastic resin (B) satisfy the relationship of D(A)<D(B).

[0030] [4] A method for producing the above-mentioned resin composition, comprising preparing a mixture of a thermoplastic resin (A) and a thermoplastic resin (B) in a molten state, and mixing the mixture with a polar resin (C).

[0031] [5] A method for producing a resin modifier comprising a thermoplastic resin (A) and a thermoplastic composition (B) for obtaining a resin composition, comprising: adding a free radical initiator in a molten state to a mixture of a thermoplastic resin (A) and a precursor (B0) of a thermoplastic resin (B) satisfying the following conditions (4) and (5), introducing a reactive functional group into the precursor (B0), and obtaining a thermoplastic resin (A) and a thermoplastic resin (B) having a reactive functional group.

[0032] (4) The thermoplastic resin (A) is a block copolymer having a block (A-1) containing more than 70 mol % of aromatic vinyl monomer units and a block (A-2) containing more than 30 mol % of conjugated diene monomer units, or a hydrogenated product thereof, and has a glass transition temperature in the range of -30 to +50°C,

[0033] (5) The glass transition temperature of the precursor (B0) of the thermoplastic resin (B) is within the range of -100 to -31°C.

[0034] Effects of the Invention

[0035] According to the present invention, it is possible to provide a resin composition which exhibits high vibration damping properties even at relatively high temperatures, has good moldability, and is excellent in impact resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 : is a schematic cross-sectional view showing an example of a core-shell structure.

[0037] Figure 2 This is an enlarged cross-sectional photograph showing an example of a core-shell structure.

[0038] Figure 3 is a schematic cross-sectional view showing another example of the core-shell structure.

[0039] Figure 4 This is an enlarged cross-sectional photograph showing another example of the core-shell structure. DETAILED DESCRIPTION

[0040] In the present specification, the provisions defined as preferred can be arbitrarily selected, and a combination of the provisions defined as preferred can be said to be more preferred.

[0041] In this specification, the description "XX to YY" means "XX or more and YY or less".

[0042] In this specification, for a preferred numerical range (e.g., content range), the lower limit and upper limit values ​​recorded in stages can be independently combined. For example, based on the description of "preferably 10 to 90, more preferably 30 to 60", the "preferable lower limit (10)" and the "preferable upper limit (60)" can also be combined to "10 to 60".

[0043] In the present specification, "~ unit" (here, "~" represents a monomer) means a "structural unit derived from ~", for example, "propylene unit" means a "structural unit derived from propylene".

[0044] In this specification, for example, "(meth)acrylic acid" means both "acrylic acid" and "methacrylic acid", and other similar terms are also the same.

[0045] In this specification, the weight average molecular weight is a weight average molecular weight calculated in terms of standard polystyrene determined by gel permeation chromatography (GPC).

[0046] [Resin composition]

[0047] A resin composition according to an embodiment of the present invention (hereinafter, sometimes referred to as a resin composition of the present embodiment) comprises a thermoplastic resin (A), a thermoplastic resin (B), and a polar resin (C).

[0048] The resin composition satisfies the following conditions (1) to (3),

[0049] (1) The thermoplastic resin (B) has at least one of a reactive functional group and a monomer unit containing a heteroatom;

[0050] (2) The thermoplastic resin (A) and the thermoplastic resin (B) are different types of resins;

[0051] (3) With respect to the total mass of the resin composition, the content of the thermoplastic resin (A) is 1 to 30 mass %, the content of the thermoplastic resin (B) is 1 to 30 mass %, and the content of the polar resin (C) is 40 to 98 mass %.

[0052] By using a thermoplastic resin (B) having high compatibility with the polar resin (C) and having at least one of a reactive functional group and a monomer unit containing a heteroatom, the thermoplastic resin (B) acts as a compatibilizer to form a core-shell structure in which the thermoplastic resin (B) is a shell and the thermoplastic resin (A) of a resin different from the thermoplastic resin (B) is a core. As a result, in the matrix of the polar resin (C), even the thermoplastic resin (A) which is difficult to be compatible with the polar resin (C) alone can be easily dispersed well in the polar resin (C).

[0053] As a result of the improved compatibility between the polar resin (C) and the thermoplastic resin (A), the property improvement effects of the thermoplastic resin (B) and the thermoplastic resin (A) are easily manifested. As the thermoplastic resin (B), a resin suitable for improving impact resistance is selected, and as the thermoplastic resin (A), a resin suitable for improving shock absorption is selected. It is believed that the impact resistance and shock absorption can be improved while having moldability.

[0054] A preferred embodiment of the above-mentioned resin composition is a resin composition, in which a core-shell structure exists in its molded product, in which the thermoplastic resin (A) and the thermoplastic resin (B) are dispersed in the polar resin (C), and the dispersion diameter D(A) of the thermoplastic resin (A) and the dispersion diameter D(B) of the thermoplastic resin (B) satisfy the relationship of D(A)<D(B).

[0055] Hereinafter, each component contained in the resin composition of this embodiment will be described. In addition, the core-shell structure, the production method, and the application etc. will be described in order.

[0056] <Thermoplastic resin (A)>

[0057] As specified in the above condition (2), the thermoplastic resin (A) is a different type of resin from the thermoplastic resin (B). In this specification, "different types of resins" means that at least one of the chemical structure, weight average molecular weight, ratio of each monomer in the case of having multiple monomer units, and polymerization form of the monomers constituting the resin is different. The "different types of resins" include a mode in which the thermoplastic resin (B) has at least one of a reactive functional group and a monomer unit containing a heteroatom, and the thermoplastic resin (A) has none of the above reactive functional groups and monomer units containing heteroatoms.

[0058] From the viewpoint of production cost, the thermoplastic resin (A) preferably has no reactive functional group. More specifically, the thermoplastic resin (A) preferably has no alkoxysilyl group, carboxyl group, amino group, hydroxyl group, epoxy group, group derived from an acid anhydride, ester group, mercapto group, or oxazoline group.

[0059] Thermoplastic resin (A) is preferably a block copolymer or a hydrogenated product thereof comprising a polymer block (A-1) mainly composed of a structural unit derived from an aromatic vinyl compound (hereinafter sometimes referred to as "aromatic vinyl compound unit") and a polymer block (A-2) mainly composed of a structural unit derived from a conjugated diene compound (hereinafter sometimes referred to as "conjugated diene unit") from the viewpoint of mechanical properties such as shock absorption and impact resistance. "Mainly" as used herein means that the polymer block (A) contains more than 50% by mass of a structural unit derived from an aromatic vinyl compound, and the polymer block (B) contains more than 50% by mass of a structural unit derived from a conjugated diene compound.

[0060] From the viewpoint of further improving mechanical properties such as shock absorption and impact resistance, a block copolymer having a block (A-1) containing more than 70 mol % of an aromatic vinyl monomer unit and a block (A-2) containing 30 mol % or more of a conjugated diene monomer or a hydrogenated product thereof is preferred.

[0061] The aromatic vinyl compound unit is more preferably 80 mol% or more, further preferably 90 mol% or more, further preferably 95 mol% or more, and particularly preferably 100 mol% in the polymer block (A-1). In other words, the aromatic vinyl compound unit in the polymer block (A-1) is preferably 80 to 100 mol%.

[0062] From the viewpoint of exhibiting excellent shock absorbing properties, the conjugated diene unit in the polymer block (A-2) is preferably 50 mol% or more, more preferably 70 mol% or more, further preferably 90 mol% or more, and particularly preferably 100 mol%. In other words, the conjugated diene unit in the polymer block (A-2) is preferably 50 to 100 mol%.

[0063] More preferably, it is a hydrogenated product of a block copolymer having a polymer block (A-1) and a polymer block (A-2), wherein the hydrogenation rate of the hydrogenated product is 50 to 99 mol %.

[0064] The glass transition temperature of the thermoplastic resin (A) is preferably in the range of -30 to +50°C, more preferably in the range of -25 to +30°C, and even more preferably in the range of -20 to +20°C.

[0065] In this specification, the glass transition temperature is a value measured using a differential scanning calorimeter (DSC) measuring apparatus.

[0066] The thermoplastic resin (A) preferably has a structure represented by the following formula (X) or a structure of a hydrogenated product thereof.

[0067] [Chemistry 1]

[0068]

[0069] (In the above formula (X), R 1 ~R 3 Each independently represents a hydrogen atom or a hydrocarbon group having 1 to 11 carbon atoms, and a plurality of R 1 ~R 3 They may be the same or different).

[0070] When a block copolymer or a hydrogenated product thereof is used as the thermoplastic resin (A), the alicyclic skeleton (X) is preferably included in a polymer block containing a structural unit derived from a conjugated diene compound as a constituent element thereof. Details of the alicyclic skeleton (X) will be described later.

[0071] It should be noted that the thermoplastic resin (A) preferably does not have a monomer unit containing a hetero atom, which allows the thermoplastic resin (B) to have a reactive functional group described below.

[0072] The details of the block copolymer or its hydrogenated product used as the thermoplastic resin (A) will be described later.

[0073] <Thermoplastic resin (B)>

[0074] As specified in the above condition (1), the thermoplastic resin (B) has at least one of a reactive functional group and a monomer unit containing a heteroatom. In addition, as specified in the above condition (2), the thermoplastic resin (B) and the thermoplastic resin (A) are different types of resins.

[0075] The reactive functional group that the thermoplastic resin (B) may have refers to a functional group that can relatively easily form a bond through a chemical reaction with another functional group.

[0076] As the above-mentioned reactive functional group, alkoxysilyl, carboxyl, amino, hydroxyl, epoxy, group derived from anhydride, ester group, mercapto, oxazoline etc. can be cited. It is also possible to have two or more of these. It is preferably one or more functional groups selected from alkoxysilyl, carboxyl, amino, hydroxyl, epoxy, group derived from anhydride, ester group and oxazoline. From the viewpoint of making the extrusion reaction easy and suitable for industrialization, it is particularly preferred as a reactive functional group to be derived from at least one group selected from maleic anhydride and alkoxysilyl. Here, "group derived from maleic anhydride" refers to a group having a structure in which one of the carbons of the double bond constituting the ring of maleic anhydride forms a bonding position.

[0077] Examples of the monomer unit containing a hetero atom include monomer units such as hexamethylenediamine containing a nitrogen atom-containing amino group, monomer units such as terephthalic acid containing an oxygen atom-containing carboxyl group, and monomer units such as sodium sulfide containing a sulfur atom. Two or more of these may be present.

[0078] The thermoplastic resin (B) is preferably a block copolymer having a polymer block (B-1) derived from an aromatic vinyl compound and a polymer block (B-2) derived from a conjugated diene compound, or a hydrogenated product thereof, modified with a compound having the aforementioned reactive functional group, or a modified product of an olefin resin modified with a compound having the aforementioned reactive functional group. In the former case, a block copolymer having a block (B-1) containing more than 70 mol% of an aromatic vinyl monomer unit and a block (B-2) containing 30 mol% or more of a conjugated diene monomer, or a hydrogenated product thereof, modified with a compound having the aforementioned reactive functional group, is more preferably used.

[0079] The details of the block copolymer or its hydrogenated product used to obtain the thermoplastic resin (B) will be described later.

[0080] Examples of the olefin resin used to obtain the thermoplastic resin (B) include polyethylenes such as high-density polyethylene, medium-density polyethylene, low-density polyethylene, and linear low-density polyethylene; polypropylenes (PP) such as homopolypropylene, block polypropylene, and random polypropylene; homopolymers or copolymers of α-olefins; copolymers of propylene and / or ethylene with α-olefins, etc. Examples of the α-olefins include α-olefins having a carbon number of 20 or less, such as 1-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, 3-methyl-1-pentene, 4-methyl-1-pentene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, and 1-eicosene, and one or more of these can be used.

[0081] When an olefin resin is used as the thermoplastic resin (B), it is preferable to use a modified olefin resin obtained by modifying these olefin resins with maleic acid or the like, that is, a modified olefin resin.

[0082] As preferred thermoplastic resins (B) having reactive functional groups, there can be cited epoxy-containing resins such as epoxy-containing ethylene copolymers, epoxides of diene polymers, epoxy-containing graft copolymers, epoxy-containing acrylic copolymers, and epoxy-containing styrene copolymers; and oxazoline-containing compounds such as oxazoline-containing styrene copolymers. If an epoxy-containing resin is used as the thermoplastic resin (B), the polar resin (C) is dispersed in the thermoplastic resin (A) in a substantially smaller amount than other thermoplastic resins (B). It should be noted that if a thermoplastic resin (B) different from the epoxy-containing resin is used, it is easy to increase the amount used, but it is easy to evenly disperse the thermoplastic resin (B) in the resin composition, which has the advantage of stabilizing the feed amount during continuous production such as extrusion molding.

[0083] (Epoxy-containing vinyl copolymer)

[0084] The epoxy-group-containing ethylene-based copolymer is a copolymer including a structural unit derived from ethylene and a structural unit derived from glycidyl methacrylate.

[0085] The content of the structural unit derived from glycidyl methacrylate in the epoxy-containing ethylene-based copolymer is not particularly limited, but is preferably 3 to 30% by mass, more preferably 5 to 25% by mass, and particularly preferably 10 to 20% by mass, when the mass of the copolymer is 100% by mass, from the viewpoint of compatibilization effect.

[0086] In addition, the content of the structural unit derived from glycidyl methacrylate was measured by infrared spectroscopy.

[0087] The epoxy-containing ethylene copolymer may be an epoxy-containing ethylene copolymer consisting only of structural units derived from ethylene and structural units derived from glycidyl methacrylate, or may be an epoxy-containing ethylene copolymer further comprising structural units derived from ethylene, structural units derived from glycidyl methacrylate, and structural units derived from one or more compounds selected from the group consisting of the compound represented by the following formula (1) and the compound represented by the following formula (2).

[0088] CH2=CR 4 R 5 (1)

[0089] CHR 6 =CHR 7 (2)

[0090] In the formula,

[0091] R 4 represents a hydrogen atom or an alkyl group having 1 to 8 carbon atoms,

[0092] R 5 Represents a halogen atom, or -COOR 8 The group (R 8 represents an alkyl group having 1 to 8 carbon atoms),

[0093] R 6 represents a hydrogen atom, an alkyl group having 1 to 8 carbon atoms, or -COOR 9 The group (R 9 represents an alkyl group having 1 to 8 carbon atoms),

[0094] R 7 represents an alkylnitrile having 1 to 8 carbon atoms, an alkyl ether group, an alkylamide group, a halogen atom, a phenyl group, or -COOR 10 The group (R 10 represents an alkyl group having 1 to 8 carbon atoms, or R 10 Represents -OCOR 11 The group (R 11 represents an alkyl group having 1 to 8 carbon atoms).

[0095] Examples of the compound represented by formula (1) include propylene, 1-butene, vinyl acetate, acrylic acid, methacrylic acid, methyl acrylate, ethyl acrylate, methyl methacrylate, ethyl methacrylate, vinyl chloride, vinylidene chloride, styrene, acrylonitrile, isobutyl vinyl ether, and acrylamide. One of these compounds may be used alone, or two or more thereof may be used. Among these compounds, vinyl acetate, methyl acrylate, and methyl methacrylate are preferred.

[0096] Examples of the compound represented by formula (2) include dimethyl maleate, diethyl maleate, dimethyl fumarate, and diethyl fumarate.

[0097] When the epoxy-containing ethylene copolymer comprises a structural unit derived from ethylene, a structural unit derived from glycidyl methacrylate, and a structural unit derived from a compound represented by formula (1) or formula (2), the content of the monomer unit derived from the compound represented by formula (1) or formula (2) is not particularly limited, and when the mass of the copolymer is set to 100 mass%, it is preferably 40 mass% or less, and more preferably 30 mass% or less. In addition, in the above case, the content of the monomer unit derived from glycidyl methacrylate is not particularly limited, and when the mass of the copolymer is set to 100 mass%, it is preferably 2 to 20 mass%, more preferably 3 to 10 mass%, and particularly preferably 5 to 7 mass%.

[0098] Examples of the epoxy group-containing ethylene copolymer include ethylene-glycidyl methacrylate copolymer, ethylene-propylene-glycidyl methacrylate copolymer, ethylene-butene-1-glycidyl methacrylate copolymer, ethylene-vinyl acetate-glycidyl methacrylate copolymer, ethylene-acrylic acid-glycidyl methacrylate copolymer, ethylene-methacrylic acid-glycidyl methacrylate copolymer, ethylene-methyl acrylate-glycidyl methacrylate copolymer, ethylene-ethyl acrylate-glycidyl methacrylate copolymer, ethylene-methyl methacrylate-glycidyl methacrylate copolymer, ethylene-ethyl methacrylate-glycidyl methacrylate copolymer, ethylene-methyl methacrylate-glycidyl methacrylate copolymer, and ethylene-ethyl methacrylate-glycidyl methacrylate copolymer. Oil-based ester copolymers, ethylene-methyl maleate-glycidyl methacrylate copolymers, ethylene-ethyl maleate-glycidyl methacrylate copolymers, ethylene-methyl fumarate-glycidyl methacrylate copolymers, ethylene-ethyl fumarate-glycidyl methacrylate copolymers, ethylene-vinyl chloride-glycidyl methacrylate copolymers, ethylene-vinylidene chloride-glycidyl methacrylate copolymers, ethylene-styrene-glycidyl methacrylate copolymers, ethylene-acrylonitrile-glycidyl methacrylate copolymers, ethylene-isobutyl vinyl ether-glycidyl methacrylate copolymers, ethylene-acrylamide-glycidyl methacrylate copolymers, and the like.

[0099] It can be used alone or in combination. Among these, preferably ethylene-glycidyl methacrylate copolymer (e.g., Sumitomo Chemical Co., Ltd., Bondo Filter BF-E, ethylene unit: 88 mass %, glycidyl methacrylate unit: 12 mass %), ethylene-methyl acrylate-glycidyl methacrylate copolymer (e.g., Sumitomo Chemical Co., Ltd., Bondo Filter BF-7M, ethylene unit: 67 mass %, glycidyl methacrylate unit: 6 mass %, methyl acrylate unit 27 mass %).

[0100] The epoxy group-containing vinyl copolymer can be synthesized by various methods, for example, by bulk polymerization, emulsion polymerization, solution polymerization, etc. using a free radical initiator.

[0101] It should be noted that representative polymerization methods include methods described in Japanese Patent Application Laid-Open No. 48-11388 and Japanese Patent Application Laid-Open No. 61-127709, etc., and polymerization under a pressure of 500 kg / cm in the presence of a polymerization initiator that generates free radicals. 2 The above method is a copolymerization method under the condition of temperature 40~300℃.

[0102] In addition, there can be mentioned a method in which an unsaturated epoxy compound and a free radical generator are mixed with a polymer comprising structural units derived from ethylene and optionally comprising structural units derived from a compound represented by formula (1) or formula (2), and the mixture is melt-grafted and copolymerized in an extruder; or a method in which ethylene and an unsaturated epoxy compound, and further an optional compound represented by formula (1) or formula (2), are copolymerized in an inert medium such as water or an organic solvent in the presence of a free radical generator.

[0103] (Epoxide of Diene Polymer)

[0104] The epoxide of a diene polymer is a polymer obtained by epoxidizing a diene polymer with an epoxidizing agent to introduce an epoxy group into the molecule.

[0105] As the diene polymer used in the epoxide of the diene polymer, butadiene polymer, styrene-butadiene copolymer, isoprene polymer, styrene-isoprene copolymer and acrylonitrile-butadiene copolymer etc. can be enumerated. It can be used alone 1 kind, also can use 2 or more kinds. Among these, from the viewpoint of improving compatibility, the epoxide of the styrene-butadiene block copolymer using styrene-butadiene copolymer is particularly preferred.

[0106] Examples of the styrene-butadiene block copolymer epoxides include styrene-butadiene block copolymer epoxides represented by the following general formula (3) and the following general formula (4).

[0107] [Chemistry 2]

[0108]

[0109] Examples of commercially available products of epoxides of styrene-butadiene block copolymers include Epiflex AT501 and Epiflex CT310 manufactured by Daicell Corporation.

[0110] (Oxazoline-containing styrene copolymer)

[0111] The oxazoline group-containing styrene-based copolymer is a copolymer including a structural unit derived from styrene and a structural unit derived from an oxazoline group-containing olefin such as isopropenyloxazoline.

[0112] The content of the structural unit derived from the oxazoline group-containing olefin in the oxazoline group-containing styrene copolymer is not particularly limited, but is preferably 2 to 50% by mass, more preferably 10 to 45% by mass, and particularly preferably 15 to 40% by mass, when the mass of the copolymer is 100% by mass, from the viewpoint of the compatibilization effect.

[0113] The total content of the structural units derived from styrene and the structural units derived from the oxazoline group-containing olefin relative to the total mass of the oxazoline group-containing styrene copolymer is preferably 50 to 100 mass %, more preferably 70 to 100 mass %, further preferably 85 to 100 mass %, and most preferably 100 mass %.

[0114] In addition, the presence or absence of the structural unit derived from the oxazoline group-containing olefin and the content thereof were measured by NMR.

[0115] Examples of commercially available products of the oxazoline group-containing styrene-based copolymer include EPOCLOSE RPS-1005 and PX-3-RP-5, which are copolymers of styrene and 2-isopropenyl-2-oxazoline, manufactured by Nippon Catalyst Co., Ltd.

[0116] (Epoxy-containing graft copolymer)

[0117] The epoxy group-containing graft copolymer is a graft copolymer in which a polymer having an epoxy group is introduced as a side chain into a main chain derived from a polyolefin or an acrylonitrile-styrene copolymer.

[0118] The mass ratio of the portion derived from the epoxy-containing polymer in the epoxy-containing graft copolymer is not particularly limited, but is preferably 1 to 50 mass %, more preferably 3 to 40 mass %, and particularly preferably 5 to 30 mass % when the mass of the graft copolymer is 100 mass %, from the viewpoint of easily ensuring good compatibilization.

[0119] In addition, the presence or absence of the epoxy group-containing polymer part in the epoxy group-containing graft copolymer and the content thereof were measured by NMR.

[0120] Commercially available products of the epoxy group-containing graft copolymer include the NOF Corporation Modippa A4100, A4300, A4400 and other Modippa A4000 series graft copolymers having polyolefin as the main chain and vinyl polymers such as polystyrene as the side chains.

[0121] (Epoxy-containing acrylic copolymer, epoxy-containing styrene copolymer)

[0122] The epoxy-containing acrylic copolymer is a copolymer of a polymerizable unsaturated compound having an epoxy group and an acrylic polymerizable unsaturated compound. The epoxy-containing styrene copolymer is a copolymer of a polymerizable unsaturated compound having an epoxy group and a styrene polymerizable unsaturated compound.

[0123] The content of the structural unit derived from the polymerizable unsaturated compound having an epoxy group in these epoxy-containing copolymers is not particularly limited, but is preferably 5 to 80% by mass, more preferably 10 to 70% by mass, and particularly preferably 20 to 60% by mass, when the mass of the copolymer is 100% by mass, from the viewpoint of the compatibilization effect.

[0124] In addition, the presence or absence of the structural unit derived from the polymerizable unsaturated compound having an epoxy group and the content thereof were measured by NMR.

[0125] Examples of commercially available epoxy-containing acrylic copolymers or epoxy-containing styrene copolymers include Mapluf G series (registered trademark) G-0105SA, G-0130SP, G-0150M, G-0250SP, and G-1005S manufactured by NOF Corporation.

[0126] <Polar resin (C)>

[0127] Polar resin (C) refers to a resin having polar groups such as carboxyl, sulfonic acid, hydroxyl, and cyano groups, a resin having ether bonds, ester bonds, amide bonds, thioether bonds, and the like in the resin, a resin containing at least one of oxygen, nitrogen, sulfur, and halogen in the molecule, and the like, and is a resin having polarized electrons in the molecule and having thermoplastic properties. Polar resin (C) is preferably a resin having polar groups such as sulfonic acid, cyano groups, a resin having ether bonds, ester bonds, amide bonds, thioether bonds, and the like in the resin, a resin containing at least one of oxygen, nitrogen, sulfur, and halogen in the molecule, and more preferably a resin containing at least one of ether bonds, ester bonds, and amide bonds in the resin.

[0128] Preferably, it is a polyamide resin such as nylon 6, nylon 66, nylon 610, nylon 9, nylon 6 / 66, nylon 66 / 610, nylon 6 / 11, nylon 6 / 12, nylon 12, nylon 46, and amorphous nylon; a polyester resin such as polyethylene terephthalate, polyethylene naphthalate, and polybutylene terephthalate; a polyacetal resin such as polyoxymethylene homopolymer and polyoxymethylene copolymer; a polyphenylene sulfide (PPS) resin, polyphenylene ether resin, polyarylate resin, polyethersulfone resin, epoxy resin, polyurethane resin, polyvinyl alcohol resin, polycarbonate resin, ethylene-vinyl acetate copolymer, ethylene-methacrylic acid copolymer, polyether ketone, polyether ether ketone, polyvinyl chloride, polyvinylidene chloride, polyacrylonitrile, vinylon, triacetyl cellulose, ABS resin, AS resin, ACS resin, xylene resin, acrylic resin, and at least one selected from polyester-based thermoplastic elastomers. More preferably, it is at least one selected from the group consisting of polyamide resins, polyester resins, polyacetal resins, polyphenylene sulfide resins, polyurethane resins, polyvinyl alcohol resins, polycarbonate resins, and polyester-based thermoplastic elastomers.

[0129] The polyester-based thermoplastic elastomer used as the polar resin (C) can be obtained, for example, by polycondensing oligomers obtained by esterification or transesterification using (i) aliphatic and / or alicyclic diols having 2 to 12 carbon atoms, (ii) aromatic dicarboxylic acids or their alkyl esters, and (iii) polyalkylene ether glycol as raw materials.

[0130] Examples of commercially available polyester-based thermoplastic elastomers include Hitrel 3046 (registered trademark) manufactured by Dupont Toray Co., Ltd.

[0131] At least one of the glass transition temperature and the melting point of the polar resin (C) is preferably 80° C. or higher, more preferably 100° C. or higher, and even more preferably 150° C. or higher.

[0132] In this specification, the melting point is measured by a DSC measuring apparatus.

[0133] When at least one of the glass transition temperature and the melting point is within the above range, the mechanical properties of the composition become good.

[0134] <Resin content ratio>

[0135] As specified in the above condition (3), the content of the thermoplastic resin (A) is 1 to 30 mass %, the content of the thermoplastic resin (B) is 1 to 30 mass %, and the content of the polar resin (C) is 40 to 98 mass % relative to the total mass of the resin composition.

[0136] By setting the contents of the thermoplastic resin (A), the thermoplastic resin (B) and the polar resin (C) (hereinafter sometimes referred to as resins (A) to (C)) within the above ranges, in a molded article of the resin composition, the core-shell structure described later is easily dispersed in the polar resin (C).

[0137] From the viewpoint of further improving dispersibility, the content of the thermoplastic resin (A) is more preferably 2 to 20% by mass, the content of the thermoplastic resin (B) is 2 to 20% by mass, and the content of the polar resin (C) is more preferably 50 to 96% by mass. It is still more preferred that the content of the thermoplastic resin (A) is 3 to 15% by mass, the content of the thermoplastic resin (B) is 2 to 15% by mass, and the content of the polar resin (C) is 70 to 95% by mass.

[0138] When the above-mentioned epoxy group-containing resin is used as the thermoplastic resin (B), the polar resin (C) can be easily dispersed in a substantially smaller amount compared to other thermoplastic resins (B).

[0139] When an epoxy group-containing resin is used as the thermoplastic resin (B), the content of the thermoplastic resin (A), the content of the thermoplastic resin (B), and the content of the polar resin (C) are preferably 3 to 30% by mass, 1 to 10% by mass, and 60 to 96% by mass. More preferably, the content of the thermoplastic resin (A), the content of the thermoplastic resin (B), the content of the polar resin (C), and the content of the polar resin (C) are 5 to 25% by mass, 1 to 8% by mass, and 67 to 94% by mass. Even more preferably, the content of the thermoplastic resin (A), the content of the thermoplastic resin (B), the content of the polar resin (C), and the content of the polar resin (C) are 7 to 20% by mass, 1 to 5% by mass, and 75 to 92% by mass.

[0140] <Core-shell structure>

[0141] The resin composition has a core-shell structure in its molded product, in which a thermoplastic resin (A) and a thermoplastic resin (B) are dispersed in a polar resin (C), and the dispersion diameter D(A) of the thermoplastic resin (A) and the dispersion diameter D(B) of the thermoplastic resin (B) satisfy the relationship D(A)<D(B).

[0142] Here, the dispersion diameter refers to the volume average dispersion diameter. In addition, the core-shell structure includes a domain region containing one or more thermoplastic resins (A) in the shell of the thermoplastic resin (B). In addition, it can also include a core-shell structure containing one or more domain regions of polar resins (C) in the shell of the thermoplastic resin (B); a core-shell structure containing a domain region of thermoplastic resin (A) and a domain region of polar resin (C) in the shell of the thermoplastic resin (B). In this way, by having a core-shell structure containing multiple domain regions, it is easy to improve impact resistance.

[0143] Figure 1 : is a schematic cross-sectional view showing an example of a core-shell structure in a molded body of the resin composition according to the present embodiment. Figure 1 As shown, the core-shell structure 10 exists in the matrix 20 of the polar resin (C). The core-shell structure 10 includes a core 10a of the thermoplastic resin (A) and a shell 10b of the thermoplastic resin (B).

[0144] Figure 2 is shown with Figure 1 An enlarged cross-sectional photograph of an example of a core-shell structure of the corresponding structure, taken using a transmission electron microscope (TEM). Figure 2 As shown, a core-shell structure is formed in which the thermoplastic resin (B) is a shell and the thermoplastic resin (A) is a core in the matrix of the polar resin (C). It should be noted that the large number of dots inside the core are obtained by dyeing specific parts of the thermoplastic resin (A).

[0145] Figure 3: is a cross-sectional schematic diagram showing another example of the core-shell structure in the molded body of the resin composition involved in this embodiment. Figure 3 As shown, the core-shell structure 11 includes a plurality of domains distributed in an island shape within a shell 11b of a thermoplastic resin (B). The plurality of domains include a domain 11a of a thermoplastic resin (A) and a domain 11c of a polar resin (C).

[0146] Figure 4 is shown with Figure 3 The enlarged cross-sectional photograph of another example of the core-shell structure corresponding to the structure. Figure 4 As shown, the core-shell structure includes a plurality of domains distributed in an island shape in the core, and among these domains, a plurality of domains of the thermoplastic resin (A) and a plurality of domains of the polar resin (C) exist in the shell of the thermoplastic resin (B).

[0147] The volume average dispersion diameter of the core-shell structure in the molded product of the resin composition is preferably 0.01 to 10 μm, more preferably 0.03 to 8 μm, and even more preferably 0.05 to 6 μm. It should be noted that the dispersion diameter D(B) of the thermoplastic resin (B) is substantially the same as the volume average dispersion diameter of the core-shell structure.

[0148] The dispersion diameter D(A) of the thermoplastic resin (A) is preferably 0.01 to 8 μm, more preferably 0.02 to 6 μm, and even more preferably 0.03 to 4 μm.

[0149] When the volume average dispersion diameter of the core-shell structure is within the above numerical range, the dispersibility of the core-shell structure in the polar resin (C) can be improved, and the mechanical properties of the resin composition can be improved.

[0150] It should be noted that, when the core-shell structure is an ellipse or other non-circular shape, the average of the measured values ​​of the major axis length is recorded as the volume average dispersion diameter, and the dispersion diameter D(A) and the dispersion diameter D(B) are each expressed using the major axis length. Figure 3 , Figure 4 As shown, when a plurality of domains of the thermoplastic resin (A) exist within the shell of the thermoplastic resin (B), D(A) is represented by the major axis length of the domain of the thermoplastic resin (A) having the largest diameter.

[0151] <Additives>

[0152] The resin composition may contain various additives within a range not impairing the effects of the present invention.

[0153] Examples of the additive include inorganic fillers such as talc, clay, mica, calcium silicate, glass, glass hollow spheres, glass fibers, calcium carbonate, magnesium carbonate, basic magnesium carbonate, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, zinc borate, dawsonite, ammonium polyphosphate, calcium aluminate, hydrotalcite, silica, diatomaceous earth, aluminum oxide, titanium oxide, iron oxide, zinc oxide, magnesium oxide, tin oxide, antimony oxide, barium ferrite, strontium ferrite, carbon black, graphite, carbon fiber, activated carbon, carbon hollow spheres, calcium titanate, lead zirconate titanate, silicon carbide, and mica; and organic fillers such as wood flour and starch. Examples of the additives include tackifying resins, plasticizers, fillers, crosslinking agents (isocyanate crosslinking agents, epoxy crosslinking agents, metal chelate crosslinking agents, aziridine crosslinking agents, amine resins, etc.), heat stabilizers, light stabilizers, ultraviolet absorbers, infrared absorbers, antioxidants, lubricants, colorants, antistatic agents, flame retardants, water repellents, waterproofing agents, hydrophilicity-imparting agents, electrical conductivity-imparting agents, thermal conductivity-imparting agents, electromagnetic wave shielding agents, light transmittance adjusters, fluorescent agents, slip agents, transparency-imparting agents, anti-blocking agents, metal inertizing agents, antibacterial agents, crystal nucleating agents, crack prevention agents, ozone degradation prevention agents, rodent repellents, dispersants, thickeners, light resistance agents, weather resistance agents, copper corrosion inhibitors, reinforcing agents, mildew prevention agents, and macrocyclic molecules (cyclodextrin, calixarene, pumpkin ring, etc.).

[0154] The above additives may be used alone or in combination of two or more.

[0155] The content of the above-mentioned additive in resin combination is not limited, and can be appropriately adjusted according to the type of the additive, the purposes of resin combination, etc. When resin combination contains the above-mentioned additive, the content of the above-mentioned additive can be, for example, less than 50 mass %, less than 45 mass %, less than 30 mass %, less than 20 mass %, less than 10 mass %, relative to the total amount 100 mass % of resin combination, and can be more than 0.01 mass %, more than 0.1 mass %, more than 1 mass %, more than 5 mass %. In other words, the content of the additive in resin combination is preferably 0.01~50 mass %.

[0156] <Block copolymer or hydrogenated product thereof>

[0157] As the thermoplastic resin (A), the block copolymer or its hydrogenated product which can be used to obtain the thermoplastic resin (B), the constituent components, the proportion used, the properties, etc. are described.

[0158] (Structure of polymer block (A-1))

[0159] The polymer block (A-1) constituting the block copolymer preferably has a structural unit derived from an aromatic vinyl compound used as a monomer from the viewpoint of mechanical properties such as shock absorbing properties and impact resistance.

[0160] The polymer block (A-1) preferably contains more than 70 mol% of a structural unit derived from an aromatic vinyl compound (hereinafter sometimes referred to as "aromatic vinyl compound unit") in the polymer block (A-1), and from the viewpoint of mechanical properties such as impact resistance, it is more preferably 80 mol% or more, further preferably 90 mol% or more, further preferably 95 mol% or more, and particularly preferably 100 mol%. In other words, the content of the structural unit derived from the aromatic vinyl compound in the polymer block (A-1) is preferably more than 70 mol% and 100 mol% or less.

[0161] Examples of the aromatic vinyl compound include styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, α-methylstyrene, β-methylstyrene, 2,6-dimethylstyrene, 2,4-dimethylstyrene, α-methyl-o-methylstyrene, α-methyl-m-methylstyrene, α-methyl-p-methylstyrene, β-methyl-o-methylstyrene, β-methyl-m-methylstyrene, β-methyl-p-methylstyrene, 2,4,6-trimethylstyrene, α-methyl-2,6-dimethylstyrene, α-methyl-2,4-dimethylstyrene, β-methyl-2,6-dimethylstyrene, β-methyl-2,4-dimethylstyrene, o-chlorostyrene, m-chlorostyrene, p-chlorostyrene, 2,6-dichlorostyrene, 2,4- Dichlorostyrene, α-chloro-o-chlorostyrene, α-chloro-m-chlorostyrene, α-chloro-p-chlorostyrene, β-chloro-o-chlorostyrene, β-chloro-m-chlorostyrene, β-chloro-p-chlorostyrene, 2,4,6-trichlorostyrene, α-chloro-2,6-dichlorostyrene, α-chloro-2,4-dichlorostyrene, β-chloro-2,6-dichlorostyrene, β-chloro-2,4-dichlorostyrene, o-tert-butylstyrene, m-tert-butylstyrene, p-tert-butylstyrene, o-methoxystyrene, m-methoxystyrene, p-methoxystyrene, o-chloromethylstyrene, m-chloromethylstyrene, p-chloromethylstyrene, o-bromomethylstyrene, m-bromomethylstyrene, p-bromomethylstyrene, styrene derivatives substituted with silyl, indene, vinylnaphthalene, N-vinylcarbazole, etc. These aromatic vinyl compounds can be used alone or in combination. Among them, from the viewpoint of manufacturing cost and physical property balance, preferably styrene, α-methylstyrene, p-methylstyrene, and mixtures thereof, more preferably styrene.

[0162] Without hindering the purpose and effect of the present invention, the polymer block (A-1) may contain a structural unit derived from an unsaturated monomer other than an aromatic vinyl compound (hereinafter sometimes referred to as "other unsaturated monomer unit"), and the content of the structural unit in the polymer block (A-1) is preferably 30 mol% or less, more preferably less than 20 mol%, further preferably less than 15 mol%, further preferably less than 10 mol%, further preferably less than 5 mol%, and particularly preferably 0 mol%. In other words, the content of the other unsaturated monomer unit in the polymer block (A-1) is preferably 0 to 30 mol%.

[0163] Examples of the other unsaturated monomer include at least one selected from butadiene, isoprene, 2,3-dimethylbutadiene, 1,3-pentadiene, 1,3-hexadiene, isobutylene, methyl methacrylate, methyl vinyl ether, β-pinene, 8,9-menthene, dipentene, methylene norbornene, 2-methylenetetrahydrofuran, etc. The bonding form of the polymer block (A-1) containing the other unsaturated monomer unit is not particularly limited, and may be random or tapered.

[0164] The block copolymer has at least one of the aforementioned polymer blocks (A-1). In the case where the block copolymer has two or more polymer blocks (A-1), these polymer blocks (A-1) may be the same or different. It should be noted that in this specification, "different polymer blocks" refer to the monomer units constituting the polymer blocks, the weight-average molecular weight, the stereoregularity, and the ratio of each monomer unit in the case of having a plurality of monomer units and the copolymerization morphology (random, gradient, block) in which at least one is different.

[0165] (Weight Average Molecular Weight of Polymer Block (A-1))

[0166] The weight average molecular weight (Mw) of the polymer block (A-1) is not particularly limited, and the weight average molecular weight of at least one polymer block (A-1) among the polymer blocks (A-1) of the block copolymer is preferably 3,000 to 60,000, more preferably 4,000 to 50,000. The block copolymer can contribute to further improvement of the vibration damping property by having at least one polymer block (A-1) having a weight average molecular weight within the above range.

[0167] In addition, the weight average molecular weight is a weight average molecular weight calculated|required by gel permeation chromatography (GPC) measurement and standard polystyrene conversion.

[0168] (Content of polymer block (A-1))

[0169] The content of the polymer block (A-1) in the block copolymer is preferably 50% by mass or less, more preferably 30% by mass or less, more preferably 16% by mass or less, particularly preferably 14% by mass or less. If it is 50% by mass or less, it is possible to prepare a block copolymer or its hydride with moderate flexibility, tan δ peak strength without reducing and excellent shock absorption. In addition, the lower limit is preferably 1% by mass or more, more preferably 3% by mass or more, more preferably 6% by mass or more. If it is 1% by mass or more, it is possible to prepare a block copolymer or its hydride with mechanical properties such as impact resistance, molding processability and coating properties suitable for various uses of resin composition. In other words, the content of the polymer block (A-1) in the block copolymer is preferably 1~50% by mass.

[0170] It should be noted that the content of the polymer block (A-1) in the block copolymer is determined by 1 More specifically, the values ​​obtained by H-NMR measurement are values ​​measured according to the method described in Examples.

[0171] (Structure of polymer block (A-2))

[0172] The polymer block (A-2) constituting the block copolymer is a structural unit derived from a conjugated diene compound. The polymer block (A-2) preferably has a structural unit containing one or more alicyclic skeletons (X) represented by the following formula (X) in the main chain (hereinafter sometimes referred to as "units containing alicyclic skeletons"). In addition, the polymer block (A-2) may also contain a structural unit derived from a conjugated diene compound that does not contain an alicyclic skeleton (X) (hereinafter sometimes referred to as "conjugated diene unit").

[0173] The total amount of the alicyclic skeleton-containing unit and the conjugated diene unit in the polymer block (A-2) is preferably 50 mol% or more, more preferably 70 mol% or more, further preferably 90 mol% or more, and substantially particularly preferably 100 mol% from the viewpoint of exhibiting excellent vibration damping properties. In other words, the total amount of the alicyclic skeleton-containing unit and the conjugated diene unit in the polymer block (A-2) is preferably 50 to 100 mol%.

[0174] When the block copolymer has two or more polymer blocks (A-2), these polymer blocks (A-2) may be the same or different.

[0175] [Chemistry 3]

[0176]

[0177] In the above formula (X), R 1 ~R 3Each independently represents a hydrogen atom or a hydrocarbon group having 1 to 11 carbon atoms, and a plurality of R 1 ~R 3 Each may be the same or different. The number of carbon atoms in the hydrocarbon group is preferably 1 to 5, more preferably 1 to 3, and even more preferably 1 (i.e., methyl). In addition, the hydrocarbon group may be a straight chain or a branched chain, and may be a saturated or unsaturated hydrocarbon group. From the viewpoint of physical properties and the formation of the alicyclic skeleton (X), R 1 ~R 3 Particularly preferred are each independently a hydrogen atom or a methyl group.

[0178] When the block copolymer is hydrogenated, the vinyl group in the above formula (X) may be hydrogenated to form a hydrogenated product. Therefore, the alicyclic skeleton (X) in the hydrogenated product also includes a skeleton obtained by hydrogenating the vinyl group in the above formula (X).

[0179] The polymer block (A-2) is a structural unit derived from a conjugated diene compound, and the alicyclic skeleton (X) is derived from the conjugated diene compound. The alicyclic skeleton (X) is generated by anionic polymerization of a conjugated diene compound by the method described below, and at least one alicyclic skeleton (X) is contained in the main chain of the unit containing the alicyclic skeleton according to the conjugated diene compound used. The alicyclic skeleton (X) is incorporated into the main chain of the structural unit contained in the polymer block (A-2), and the molecular motion becomes small, so that the glass transition temperature is increased, and the peak strength of tanδ near room temperature is increased, which can show excellent shock absorption.

[0180] Examples of the conjugated diene compound include butadiene, isoprene, hexadiene, 2,3-dimethyl-1,3-butadiene, 2-phenyl-1,3-butadiene, 1,3-pentadiene, 2-methyl-1,3-pentadiene, 1,3-hexadiene, 1,3-octadiene, 1,3-cyclohexadiene, 2-methyl-1,3-octadiene, 1,3,7-octatriene, farnesene, myrcene, and chloroprene. Among them, butadiene, isoprene, or a combination of butadiene and isoprene is preferably used.

[0181] When butadiene and isoprene are used in combination, their mixing ratio [isoprene / butadiene] (mass ratio) is not particularly limited, but is preferably 5 / 95 to 95 / 5, more preferably 10 / 90 to 90 / 10, further preferably 40 / 60 to 70 / 30, and particularly preferably 45 / 55 to 65 / 35. In addition, when the mixing ratio [isoprene / butadiene] is expressed as a molar ratio, it is preferably 5 / 95 to 95 / 5, more preferably 10 / 90 to 90 / 10, further preferably 40 / 60 to 70 / 30, and particularly preferably 45 / 55 to 55 / 45.

[0182] As a specific example, when butadiene, isoprene, or a combination of butadiene and isoprene is used as the conjugated diene compound, the alicyclic skeleton (X) mainly produced will be described.

[0183] When butadiene is used alone as the conjugated diene compound, an alicyclic skeleton (X) having a combination of substituents as shown below (i) is generated. That is, in this case, the alicyclic skeleton (X) only forms R 1 ~R 3 Therefore, as an example of a preferred embodiment of the block copolymer or its hydrogenated product, the polymer block (A-2) has a main chain containing R 1 ~R 3 A substance having a structural unit of an alicyclic skeleton (X) which is also a hydrogen atom.

[0184] When isoprene is used alone as the conjugated diene compound, two types of alicyclic skeletons (X) having a combination of the following substituents (v) and (vi) are mainly generated.

[0185] When butadiene and isoprene are used in combination as the conjugated diene compound, six types of alicyclic skeletons (X) having combinations of the following substituents (i) to (vi) are mainly generated.

[0186] (i):R 1 = hydrogen atom, R 2 = hydrogen atom, R 3 = Hydrogen Atom

[0187] (ii):R 1 = hydrogen atom, R 2 =Methyl, R 3 = Hydrogen Atom

[0188] (iii):R 1 = hydrogen atom, R 2 = hydrogen atom, R 3 =Methyl

[0189] (iv):R 1 =Methyl, R 2 = hydrogen atom, R 3 = Hydrogen Atom

[0190] (v):R 1 =Methyl, R 2 =Methyl, R 3 = Hydrogen Atom

[0191] (vi):R 1 =Methyl, R 2 = hydrogen atom, R 3=Methyl.

[0192] In the above formula (X), from the viewpoint of further reducing molecular motion and further improving vibration damping properties by having a substituent being a hydrocarbon group, the at least one alicyclic skeleton (X) in the polymer block (A-2) is preferably the above R 1 ~R 3 The alicyclic skeleton (X') is an alicyclic skeleton in which at least one of the alicyclic skeletons is a hydrocarbon group having 1 to 11 carbon atoms. From the viewpoint of being able to efficiently generate the alicyclic skeleton from the conjugated diene compound and balancing mechanical properties such as shock absorption and impact resistance, the hydrocarbon group in the alicyclic skeleton (X') is more preferably a methyl group.

[0193] In particular, R 1 ~R 3 Each independently represents a hydrogen atom or a methyl group, and R 1 ~R 3 That is, the polymer block (A-2) is more preferably an alicyclic skeleton having a combination of substituents (ii) to (vi) described above, which contains at least one structural unit in the main chain.

[0194] (Vinyl Bond Amount of Polymer Block (A-2))

[0195] When the structural unit constituting the polymer block (A-2) is any one of an isoprene unit, a butadiene unit, or a mixture unit of isoprene and butadiene, as the bonding form of each of isoprene and butadiene except for the bonding form forming the alicyclic skeleton (X), in the case of butadiene, 1,2-bond and 1,4-bond can be adopted, and in the case of isoprene, 1,2-bond, 3,4-bond, and 1,4-bond can be adopted.

[0196] In the block copolymer and its hydrogenated product, the total content of the 3,4-bonded unit and the 1,2-bonded unit in the polymer block (A-2) (hereinafter sometimes referred to as "vinyl bond content") is preferably 55 to 95 mol%, more preferably 63 to 95 mol%, and further preferably 70 to 95 mol%. If it is within the above range, excellent vibration damping properties can be exhibited.

[0197] Here, the vinyl bond amount is measured by the method described in Examples. 1 The value was calculated by H-NMR measurement.

[0198] In addition, when the polymer block (A-2) consists of butadiene only, the above-mentioned "content of 3,4-bonded units and 1,2-bonded units" means "content of 1,2-bonded units" instead.

[0199] (Alicyclic skeleton (X) content of polymer block (A-2))

[0200] The polymer block (A-2) contains a structural unit containing an alicyclic skeleton (X) in the main chain. From the perspective of showing a more excellent shock absorbing effect and easily suppressing the reduction of resin power at high temperature, it is preferred that the polymer block (A-2) contains an alicyclic skeleton (X) of 1 mol% or more, more preferably 1.1 mol% or more, more preferably 1.4 mol% or more, more preferably 1.8 mol% or more, more preferably 4 mol% or more, more preferably 10 mol% or more, and particularly preferably 13 mol% or more. In addition, if the upper limit of the content of the alicyclic skeleton (X) in the polymer block (A-2) is within the range of the effect of the present invention, there is no particular restriction. From the perspective of productivity, it is preferably 40 mol% or less, 30 mol% or less, 20 mol% or less, or 18 mol% or less. In other words, the content of the alicyclic skeleton (X) in the polymer block (A-2) is preferably 1 to 40 mol%.

[0201] From the viewpoint of further improving the shock absorption, the polymer block (A-2) preferably contains 1 mol% or more of the alicyclic skeleton (X'), more preferably 1.3 mol% or more, and even more preferably 1.6 mol% or more. The upper limit of the content of the alicyclic skeleton (X') is the same as the upper limit of the content of the alicyclic skeleton (X). In other words, the content of the alicyclic skeleton (X') in the polymer block (A-2) is preferably 1 to 40 mol%.

[0202] More specifically, when isoprene is used as the conjugated diene compound, when butadiene is used, or when butadiene and isoprene are used in combination, the alicyclic skeleton content in each case is as follows.

[0203] When isoprene is used as the conjugated diene compound, when there is one or more alicyclic skeletons (X') having a combination of substituents (v) and (vi) in the polymer block (A-2), the total content thereof is preferably 1 mol% or more, more preferably 1.5 mol% or more, from the viewpoint of easily exhibiting a more excellent shock absorbing effect, and is further preferably 2 mol% or more, further preferably 3 mol% or more, and particularly preferably 4 mol% or more from the viewpoint of obtaining an excellent shock absorbing effect in a wide temperature range. In addition, the upper limit of the above-mentioned total content in the case of using isoprene is the same as the upper limit of the content of the alicyclic skeleton (X). In other words, the content of the alicyclic skeleton (X') having a combination of substituents (v) and (vi) in the polymer block (A-2) in the case of using isoprene is preferably 1 to 40 mol%.

[0204] When butadiene is used as a conjugated diene compound, in the polymer block (A-2), the content of the alicyclic skeleton (X) when it exists is preferably 5 mol% or more, more preferably 10 mol% or more, further preferably 15 mol% or more, further preferably 20 mol% or more, further preferably 25 mol% or more, and particularly preferably 30 mol% or more, from the viewpoint of easily showing a more excellent shock absorbing effect. In addition, the upper limit of the above content in the case of using butadiene is the same as the upper limit of the content of the alicyclic skeleton (X). In other words, the content of the alicyclic skeleton (X) in the polymer block (A-2) in the case of using butadiene is preferably 5 to 40 mol%.

[0205] When butadiene and isoprene are used in combination as conjugated diene compounds, in the polymer block (A-2), when there is one or more alicyclic skeletons (X') having a combination of substituents of the above-mentioned (ii), (iii), (v), and (vi), the total content thereof is preferably 1 mol% or more, more preferably 2 mol% or more, further preferably 5 mol% or more, further preferably 8 mol% or more, and further preferably 13 mol% or more from the viewpoint of easily showing a more excellent shock absorbing effect. The upper limit of the above-mentioned total content in the case of using butadiene and isoprene in combination is the same as the upper limit of the content of the alicyclic skeleton (X). In other words, the total content of the alicyclic skeleton (X') having a combination of substituents of the above-mentioned (ii), (iii), (v), and (vi) in the polymer block (A-2) in the case of using butadiene and isoprene in combination is preferably 1 to 40 mol%.

[0206] In addition, when butadiene and isoprene are used in combination as conjugated diene compounds, in the polymer block (A-2), when there is more than one alicyclic skeleton (X) having a combination of substituents of the above-mentioned (i) to (vi), the total content thereof is preferably 1 mol% or more, more preferably 5 mol% or more, from the viewpoint of easily showing a more excellent shock absorbing effect. The upper limit of the above-mentioned total content in the case of using butadiene and isoprene in combination is the same as the upper limit of the content of the alicyclic skeleton (X). In other words, the total content of the alicyclic skeleton (X) having a combination of substituents of (i) to (vi) in the polymer block (A-2) in the case of using butadiene and isoprene in combination is preferably 1 to 40 mol%.

[0207] It should be noted that the content of the alicyclic skeleton (X) (including (X')) contained in the block copolymer or its hydrogenated product is determined by the 13The C-NMR measurement is a value obtained from the integrated value derived from the alicyclic skeleton (X) in the polymer block (A-2), and more specifically, is a value measured according to the method described in Examples.

[0208] When the hydrogenation rate of the polymer block (A-2) is 0 mol % or more and less than 50 mol % in the block copolymer or its hydrogenated product, the molar ratio of the vinyl groups bonded to the alicyclic skeleton (X) and the vinyl groups bonded to the main chain can be determined.

[0209] For example, in the alicyclic skeleton (X') having a combination of substituents (ii), (iii), (v), and (vi), the carbon atom at the terminal of the vinyl group bonded to the alicyclic skeleton (X') (the following chemical formula (a)) 13 The chemical shift in C-NMR appears around 107 to 110 ppm, and the carbon atom at the terminal of the vinyl group bonded to the main chain (the following chemical formula (b)) 13 The chemical shift in C-NMR appears around 110-116 ppm. 13 The peak area ratio [peak area of ​​chemical shift values ​​107 to 110 ppm] / [peak area of ​​chemical shift values ​​110 to 116 ppm] measured by C-NMR is generally in the range of 0.01 to 3.00. From the viewpoint of being able to exhibit better shock absorbing properties, the area ratio is preferably 0.01 to 1.50, more preferably 0.01 to 1.00, further preferably 0.01 to 0.50, and further preferably 0.01 to 0.20.

[0210] [Chemistry 4]

[0211]

[0212] In addition, for hydrides, 13 In C-NMR measurement, almost no peaks derived from carbon atoms in the alicyclic skeleton (X) were observed, but for the substituent R 3 is a hydrocarbon group having 1 to 11 carbon atoms, the 3 The peak derived from the carbon atom on the alicyclic skeleton (X) to which the branched alkyl group of the vinyl group is bonded can be observed.

[0213] Thus, for the hydrogenated product, when the hydrogenation rate of the polymer block (A-2) is 50 to 99 mol %, it can be confirmed that the hydrogenation rate of the polymer block (A-2) is 50 to 99 mol % and the hydrogenation rate of the polymer block (A-2) is 50 to 99 mol %. 3 The molar ratio of the carbon atoms on the alicyclic skeleton (X) to which the branched alkyl group of the vinyl group is bonded and the carbon atoms on the main chain to which the branched alkyl group derived from the vinyl group is bonded.

[0214] For example, in the alicyclic skeleton (X) having a combination of substituents of (iii) and (vi), the carbon atom on the alicyclic skeleton (X) bonded to the isoprenyl group (the following chemical formula (c)) is 13 The chemical shift in C-NMR appears around 50.0 to 52.0 ppm, and the carbon atom on the main chain (the following chemical formula (d)) bonded to the isoprenyl group is 13 The chemical shift in C-NMR appears around 43.0 to 45.0 ppm. 13 The peak area ratio [peak area of ​​chemical shift values ​​50.0 to 52.0 ppm] / [peak area of ​​chemical shift values ​​43.0 to 45.0 ppm] measured by C-NMR is generally in the range of 0.01 to 3.00. From the viewpoint of being able to exhibit better shock absorbing properties, the area ratio is preferably in the range of 0.01 to 1.50, more preferably in the range of 0.01 to 1.00, further preferably in the range of 0.01 to 0.50, and further preferably in the range of 0.01 to 0.25.

[0215] In addition, the said peak area ratio can be measured by the method described in Example more specifically.

[0216] [Chemistry 5]

[0217]

[0218] (Weight Average Molecular Weight of Polymer Block (A-2))

[0219] The total weight average molecular weight of the polymer block (A-2) possessed by the block copolymer before hydrogenation is preferably 15,000 to 800,000, more preferably 50,000 to 700,000, further preferably 70,000 to 600,000, particularly preferably 90,000 to 500,000, and most preferably 130,000 to 450,000, from the viewpoint of vibration damping properties and the like.

[0220] (Other structural units in polymer block (A-2))

[0221] As long as the purpose and effect of the present invention are not hindered, polymer block (A-2) may also contain structural units derived from other polymerizable monomers except the aforementioned conjugated diene compound. In this case, in polymer block (A-2), the content of structural units derived from other polymerizable monomers except conjugated diene compounds is preferably less than 50 mol%, more preferably less than 30 mol%, further preferably less than 20 mol%, further preferably less than 10 mol%, particularly preferably 0 mol%. In other words, in polymer block (A-2), the content of structural units derived from other polymerizable monomers except conjugated diene compounds is preferably more than 0 mol% and less than 50 mol%.

[0222] As the other polymerizable monomer, preferably, for example, at least one compound selected from aromatic vinyl compounds such as styrene, α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, p-tert-butylstyrene, 2,4-dimethylstyrene, N-vinylcarbazole, vinylnaphthalene and vinylanthracene, and methyl methacrylate, methyl vinyl ether, β-pinene, 8,9-p-menthene, dipentene, methylenenorbornene, 2-methylenetetrahydrofuran, 1,3-cyclopentadiene, 1,3-cyclohexadiene, 1,3-cycloheptadiene, 1,3-cyclooctadiene and the like can be mentioned.

[0223] The block copolymer only needs to have at least one polymer block (A-2). When the block copolymer has two or more polymer blocks (A-2), these polymer blocks (A-2) may be the same or different.

[0224] (Bonding Form of Polymer Block (A-1) and Polymer Block (A-2))

[0225] As long as polymer block (A-1) and polymer block (A-2) are bonded, the bonding form of block copolymer is not limited, and can be any one of the bonding modes obtained by combining straight chain, branched chain, radial or more thereof. Wherein, the bonding form of polymer block (A-1) and polymer block (A-2) is preferably straight chain, as an example thereof, when polymer block (A-1) is represented by A, and polymer block (A-2) is represented by B, diblock copolymers shown in AB, triblock copolymers shown in ABA or BAB, tetrablock copolymers shown in ABAB, pentablock copolymers shown in ABABA or BABAB, (AB) nZ type copolymers (Z represents a coupling agent residue, and n represents an integer of more than 3) etc. can be cited. Wherein, preferably a straight chain triblock copolymer or a diblock copolymer, from the viewpoints of flexibility, ease of manufacture, etc., it is preferred to use a triblock copolymer of ABA type.

[0226] Specific examples of the ABA type triblock copolymer include styrene-hydrogenated butadiene / isoprene-styrene copolymers. That is, the block copolymer preferably contains at least styrene-hydrogenated butadiene / isoprene-styrene copolymers.

[0227] Here, in this specification, when the same polymer blocks are bonded in a linear shape via a bifunctional coupling agent, the bonded polymer blocks are treated as a whole as one polymer block. Accordingly, the above-mentioned examples are also included, and the polymer blocks that should be strictly described as YZY (Z represents a coupling residue) are represented as a whole as Y except when they need to be distinguished from the separate polymer block Y. In this specification, such polymer blocks containing coupling agent residues are treated as described above, so for example, a block copolymer containing coupling agent residues, which should strictly be described as ABZBA (Z represents a coupling agent residue), is described as ABA and treated as an example of a triblock copolymer.

[0228] (Content of polymer blocks (A-1) and (A-2))

[0229] In block copolymer, as long as the purpose and effect of the present invention are not hindered, the polymer block composed of other monomers except the aforementioned polymer block (A-1) and (A-2) may also be contained, and the total content of the aforementioned polymer block (A-1) and the aforementioned polymer block (A-2) is preferably 90% by mass or more, more preferably 95% by mass or more, and particularly preferably substantially 100% by mass. If it is 90% by mass or more, it is possible to make a resin composition that is easy to exert more excellent shock absorption. In other words, the total content of the polymer block (A-1) and the polymer block (A-2) in the above-mentioned block copolymer is preferably 90~100% by mass.

[0230] (Polymer block (B-1))

[0231] The structural units constituting the polymer block (B-1), the proportion of the structural units contained, the type of compound from which the structural units are derived, the weight average molecular weight of the polymer block (B-1), the vinyl bond amount of the polymer block (B-1), and the content of the polymer block (B-1) in the block copolymer are the same as those of the polymer block (A-1). However, when the polymer block (A-1) is different from the polymer block (B-1) and the thermoplastic resin (A) is different from the thermoplastic resin (B), at least one of the above elements of the polymer block (B-1) is different from that of the polymer block (A-1).

[0232] (Polymer block (B-2))

[0233] The structural units constituting the polymer block (B-2), the proportion of the structural units contained, the type of compound from which the structural units are derived, the weight average molecular weight of the polymer block (B-2), the vinyl bond content of the polymer block (B-2), the alicyclic skeleton (X) content of the polymer block (B-2), and the content of the polymer block (B-2) in the block copolymer are the same as those of the polymer block (A-2). However, when the polymer block (A-2) is different from the polymer block (B-2) and the thermoplastic resin (A) is different from the thermoplastic resin (B), at least one of the above elements of the polymer block (B-2) is different from that of the polymer block (A-2).

[0234] (Bonding method of polymer blocks (B-1) and (B-2))

[0235] The bonding mode of the polymer blocks (B-1) and (B-2) in the block copolymer is the same as the bonding mode of the polymer blocks (A-1) and (A-2). However, when the bonding mode of the polymer blocks (B-1) and (B-2) is different from the bonding mode of the polymer blocks (A-1) and (A-2), and the thermoplastic resin (A) and the thermoplastic resin (B) are different, the two are different from each other.

[0236] (Content of polymer blocks (B-1) and (B-2))

[0237] The content of the polymer blocks (B-1) and (B-2) in the block copolymer is the same as the content of the polymer blocks (A-1) and (A-2). However, when the content of the polymer blocks (B-1) and (B-2) is different from the content of the polymer blocks (A-1) and (A-2), and the thermoplastic resin (A) and the thermoplastic resin (B) are different, the two are different from each other.

[0238] (Weight average molecular weight of block copolymer or its hydrogenated product)

[0239] The weight average molecular weight (Mw) of the block copolymer and its hydrogenate determined by gel permeation chromatography in terms of standard polystyrene is preferably 15,000 to 800,000, more preferably 50,000 to 700,000, further preferably 60,000 to 600,000, further preferably 70,000 to 600,000, particularly preferably 90,000 to 500,000, and most preferably 130,000 to 450,000. If the weight average molecular weight of the block copolymer and its hydrogenate is 15,000 or more, the heat resistance is high, and if it is 800,000 or less, the handling property of the resin composition is good.

[0240] (Temperature and intensity of tan δ peak of block copolymer or its hydrogenate)

[0241] The tanδ (loss tangent) of a block copolymer or its hydrogenated product is the ratio of loss modulus / storage modulus at a frequency of 1 Hz in dynamic viscoelasticity measurement. The peak temperature and strength of tanδ significantly contribute to shock absorption and other physical properties. Here, the peak strength of tanδ refers to the value of tanδ when the peak of tanδ reaches the maximum. In addition, the peak temperature of tanδ refers to the temperature when the peak of tanδ reaches the maximum.

[0242] (Tan δ strength of block copolymer or its hydrogenated product)

[0243] In this specification, the peak temperature and strength of tan δ of the block copolymer or its hydrogenate are measured by pressing the block copolymer or its hydrogenate at a temperature of 230°C and a pressure of 10 MPa for 3 minutes to prepare a single-layer sheet with a thickness of 1.0 mm, cutting the single-layer sheet into a disc shape, and using it as a test piece. The measurement conditions are in accordance with JIS K 7244-10 (2005), with a strain of 0.1%, a frequency of 1 Hz, a measurement temperature of -70 to +100°C, and a heating rate of 3°C / min.

[0244] In addition, the peak temperature and tan δ intensity of the block copolymer or its hydrogenated product are values ​​measured according to the method described in Examples in more detail.

[0245] The block copolymer or its hydrogenated product can have a tan δ peak intensity of 1.0 or more by the above measurement. In a higher case, it can reach 1.5 or more, and further 1.9 or more. The higher the tan δ peak intensity, the better the physical properties such as shock absorption at the temperature. If it is 1.0 or more, sufficient shock absorption can be obtained in the actual use environment.

[0246] In addition, the block copolymer or its hydrogenated product may preferably have a tanδ peak temperature of -50°C or higher, more preferably -40°C or higher, further preferably -30°C or higher, further preferably -25°C or higher, or 0°C or higher. In addition, the upper limit of the tanδ peak temperature may be +50°C or lower, +40°C or lower, or +35°C or lower, as long as the effect range of the present invention is not impaired. The range of the tanδ peak temperature is, for example, preferably -50 to +50°C, more preferably -40 to +40°C, further preferably -30 to +30°C, and further preferably -25 to +25°C. If the tanδ peak temperature is -50°C or higher and +50°C or lower, sufficient shock absorbing properties in actual use environments can be obtained.

[0247] [Manufacturing method]

[0248] <Method for producing block copolymer>

[0249] As a method for producing a block copolymer, for example, by using one or more conjugated diene compounds as monomers and polymerizing by anionic polymerization to form a first polymer block, then adding a monomer of a second polymer block, and further adding a monomer of the second polymer block and a conjugated diene compound as needed, thereby obtaining a block copolymer. In the case of manufacturing a thermoplastic resin (A) having a structure including an alicyclic skeleton (X), for example, by using one or more conjugated diene compounds as monomers and polymerizing by anionic polymerization to form a polymer block (A-2) having a structural unit including an alicyclic skeleton (X) in the main chain, adding a monomer of a polymer block (A-1), and further adding a monomer of a polymer block (A-1) and a conjugated diene compound as needed, thereby obtaining a block copolymer.

[0250] The above-mentioned method of generating alicyclic skeleton by anionic polymerization can use known technology (for example, referring to U.S. Patent No. 3966691 specification). The alicyclic skeleton is formed at the end of the polymer due to the exhaustion of the monomer, and by further adding monomers thereto, polymerization can be started again from the alicyclic skeleton. Therefore, the presence or absence of the generation of the alicyclic skeleton and its content can be adjusted by the successive addition time of the monomers, the polymerization temperature, or the type, addition amount, combination of monomers and catalysts, etc. In addition, in the anionic polymerization method, an anionic polymerization initiator, a solvent, and a Lewis base as required can be used.

[0251] As the organic lithium compound that can be used as the polymerization initiator of anionic polymerization in the above method, for example, methyl lithium, ethyl lithium, n-butyl lithium, sec-butyl lithium, tert-butyl lithium, amyl lithium, etc. can be mentioned. In addition, as the dilithium compound that can be used as the polymerization initiator, for example, dilithium naphthalene, dilithium hexylbenzene, etc. can be mentioned.

[0252] Examples of the coupling agent include dichloromethane, dibromomethane, dichloroethane, dibromoethane, dibromobenzene, and phenyl benzoate.

[0253] The usage amount of these polymerization initiators and coupling agents is appropriately determined according to the desired weight average molecular weight of the block copolymer and its hydride. Usually, initiators such as alkyl lithium compounds and dilithium compounds are preferably used in a ratio of 0.01 to 0.2 mass parts relative to a total of 100 mass parts of monomers such as monomers of the polymer block (A) used in the polymerization and conjugated diene compounds, and in the case of using a coupling agent, preferably used in a ratio of 0.001 to 0.8 mass parts relative to a total of 100 mass parts of the aforementioned monomers.

[0254] The solvent is not particularly limited as long as it does not have a negative impact on the anionic polymerization reaction, and examples thereof include aliphatic hydrocarbons such as cyclohexane, methylcyclohexane, n-hexane, and n-pentane; aromatic hydrocarbons such as benzene, toluene, and xylene, etc. In addition, the polymerization reaction is usually carried out at a temperature of 0 to 100° C., preferably 10 to 70° C., for 0.5 to 50 hours, preferably 1 to 30 hours.

[0255] Furthermore, by adding a Lewis base as a co-catalyst during the polymerization of the conjugated diene compound, the contents of 3,4-bonds and 1,2-bonds and the content of the alicyclic skeleton (X) in the polymer block (A-2) can be increased.

[0256] As the Lewis base that can be used, there can be mentioned ethers such as dimethyl ether, diethyl ether, tetrahydrofuran, 2,2-di(2-tetrahydrofuranyl)propane (DTHFP); glycol ethers such as ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether; amines such as triethylamine, N,N,N',N'-tetramethylenediamine, N,N,N',N'-tetramethylethylenediamine (TMEDA), N-methylmorpholine; sodium or potassium salts of aliphatic alcohols such as sodium tert-butoxide, sodium tert-amyl alcohol or sodium isopentanol, or sodium dialkylcyclohexanolate, for example, sodium or potassium salts of alicyclic alcohols such as sodium menthol, etc. These Lewis bases can be used alone or in combination of two or more.

[0257] When the polymer block (A-2) and the polymer block (B-2) contain structural units derived from isoprene and / or butadiene, the amount of the Lewis base added is determined by controlling the amount of vinyl bonds of the isoprene units and / or butadiene units constituting the polymer block (A-2) and the polymer block (B-2) and the content of the alicyclic skeleton (X). Therefore, the amount of the Lewis base added is not strictly limited, but is preferably used in an amount within a range of 0.1 to 1,000 mol, preferably 1 to 100 mol, per gram atom of lithium contained in the alkyl lithium compound or dilithium compound used as a polymerization initiator.

[0258] The average feed rate of the conjugated diene compound (hereinafter sometimes referred to as "average diene feed rate") is preferably 150 kg / h or less, more preferably 110 kg / h or less, further preferably 55 kg / h or less, 45 kg / h or less, 30 kg / h or less, or 22 kg / h or less, for example, from the viewpoint of increasing the content of the alicyclic skeleton (X), per mole of active terminals. The lower limit is preferably 1 kg / h or more, more preferably 3 kg / h or more, further preferably 5 kg / h or more, 7 kg / h or more, 10 kg / h or more, or 15 kg / h or more, per mole of active terminals, for example, from the viewpoint of increasing productivity. In other words, the average diene feed rate is preferably 1 to 150 kg / h per mole of active terminals.

[0259] After the polymerization is carried out by the above method, an active hydrogen compound such as alcohols, carboxylic acids, water, etc. is added to stop the polymerization reaction, thereby obtaining a block copolymer.

[0260] <Method for producing hydride>

[0261] When the block copolymer obtained by the above-mentioned manufacturing method is made into a hydrogenated product, a hydrogenation reaction (hydrogenation reaction) is carried out in an inactive organic solvent in the presence of a hydrogenation catalyst. By the hydrogenation reaction, the carbon-carbon double bonds derived from the conjugated diene compound in the polymer block (A-2) and the polymer block (B-2) in the block copolymer are hydrogenated to produce a hydrogenated product of the block copolymer.

[0262] The hydrogenation reaction can be carried out at a hydrogen pressure of about 0.1 to 20 MPa, preferably 0.5 to 15 MPa, more preferably 0.5 to 5 MPa, a reaction temperature of about 20 to 250° C., preferably 50 to 180° C., more preferably 70 to 180° C., and a reaction time of usually about 0.1 to 100 hours, preferably 1 to 50 hours.

[0263] Examples of hydrogenation catalysts include Raney nickel; heterogeneous catalysts comprising metals such as Pt, Pd, Ru, Rh, and Ni supported on supports such as carbon, alumina, and diatomaceous earth; Ziegler catalysts comprising a combination of a transition metal compound and an alkyl aluminum compound, an alkyl lithium compound, and the like; and metallocene catalysts.

[0264] The hydride thus obtained can be obtained by solidifying the polymerization reaction liquid by injecting methanol or the like, and then heating or drying under reduced pressure, or by injecting the polymerization reaction liquid into hot water together with steam, performing so-called stripping to remove the solvent by azeotropy, and then heating or drying under reduced pressure.

[0265] Whether to use the block copolymer or the hydride can be determined according to the desired performance in various uses of the resin composition. Similarly, the degree of hydrogenation of the carbon-carbon double bonds in the polymer block (A-2) and the polymer block (B-2) when the hydride is prepared can be determined according to the desired performance in various uses of the resin composition.

[0266] For example, the higher the hydrogenation rate of the hydride is, the more the heat resistance and weather resistance of the hydride can be improved.

[0267] Therefore, the polymer block (A-2) and the polymer block (B-2) may be block copolymers or hydrogenated products thereof in which the hydrogenation rate is 0 mol% or more and (including the case of non-hydrogenation) is less than 50 mol%. In addition, the polymer block (A-2) and the polymer block (B-2) may be hydrogenated products in which the hydrogenation rate is 50 to 99 mol%.

[0268] It should be noted that the above hydrogenation rate is obtained by 1 The values ​​of the carbon-carbon double bond contents in the structural units derived from the conjugated diene compound and the alicyclic skeleton (X) in the polymer blocks (A-2) and (B-2) are determined by H-NMR measurement. More specifically, they are values ​​measured by the method described in Examples.

[0269] <Method for producing modified product>

[0270] The modified product used as the thermoplastic resin (B) can be produced by introducing the aforementioned reactive functional groups into the above block copolymer, the hydrogenated product of the above block copolymer, or the olefin resin. In the case of obtaining a modified product of the hydrogenated product of the above block copolymer, the above reactive functional groups can be introduced before or after hydrogenation. However, in the case of modification using a free radical reaction, it is preferred to introduce specific functional groups after hydrogenating the block copolymer to obtain a hydrogenated block copolymer from the viewpoint of reaction control.

[0271] The reaction for modifying a compound such as a hydrogenated block copolymer (hereinafter sometimes referred to as "modification reaction") can be performed by a known method.

[0272] The modification reaction can be carried out, for example, by dissolving the hydrogenated block copolymer to be modified in an organic solvent, adding various modifiers capable of adding the above-mentioned functional groups, and reacting at about 50 to 300° C. for about 0.5 to 10 hours.

[0273] In addition, the above-mentioned modification reaction can be carried out by, for example, melting the hydrogenated block copolymer to be modified using an extruder or the like without using a solvent, and adding various modifiers. In this case, the temperature of the modification reaction is usually above the melting point of the compound to be modified and below 400° C., preferably 90 to 350° C., more preferably 100 to 300° C., and the reaction time is usually about 0.5 to 10 minutes.

[0274] When the modification reaction is carried out in a molten state, it is preferred to add a radical initiator, and an antioxidant may be added from the viewpoint of suppressing side reactions.

[0275] When producing a modified product of the hydrogenated product of the block copolymer, the modification reaction is preferably carried out by the latter method of modification in a molten state from the viewpoint of easily achieving excellent workability, vibration damping properties and thermal stability.

[0276] That is, a preferred embodiment of the method for producing a modified hydrogenated product comprises, after hydrogenating the block copolymer to obtain a hydrogenated block copolymer, further comprising the step of introducing one or more functional groups selected from the group consisting of alkoxysilyl groups, carboxyl groups, amino groups, hydroxyl groups, epoxy groups, groups derived from acid anhydrides, ester groups, and oxazoline groups into the hydrogenated block copolymer in a molten state using a free radical initiator.

[0277] Examples of the modifier to which the functional group can be added include dimethyldiethoxysilane, tetramethoxysilane, tetraethoxysilane, 3-aminopropyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, hydroxymethyltriethoxysilane, vinylbenzyldiethylamine, vinylbenzyldimethylamine, 1-glycidyl-4-(2-pyridyl)piperazine, 1-glycidyl-4-phenylpiperazine, 1-glycidyl-4-methylpiperazine, 1-glycidyl-4-methylpiperazine, 1-glycidyl-4-methylhomopiperazine, 1-glycidylhexamethyleneimine, and tetraglycidyl-1,3-bisaminomethylcyclohexane. In addition, unsaturated carboxylic acid anhydrides such as maleic anhydride, citraconic anhydride, 2,3-dimethylmaleic anhydride, and itaconic anhydride can also be used as the modifier. Furthermore, a modifier capable of adding the above functional group may be used according to the modifier described in Japanese Patent Application Laid-Open No. 2011-132298. The above modifier may be used alone or in combination of two or more.

[0278] The amount of the modifier added may be appropriately determined so as to obtain the desired content of the functional groups. The amount of the modifier is generally about 0.01 to 10 parts by mass, preferably 0.01 to 5 parts by mass, more preferably 0.01 to 3 parts by mass, and even more preferably 0.05 to 2 parts by mass, relative to 100 parts by mass of the compound to be modified.

[0279] As the free radical initiator, organic peroxides or organic peresters such as dialkyl peroxides, diacyl peroxides, peroxyesters, peroxyketals, dialkyl peroxides, and hydroperoxides can be used, and azo compounds such as azobisisobutyronitrile and dimethylazoisobutyrate can also be used. Among the above-mentioned free radical initiators, organic peroxides are preferred, and dialkyl peroxides are more preferred.

[0280] The amount of the radical initiator added when producing the modified hydrogenated product may be appropriately determined depending on the combination of the hydrogenated block copolymer and the modifier. The amount of the radical initiator added is generally about 0.01 to 10 parts by mass, preferably 0.01 to 5 parts by mass, more preferably 0.01 to 3 parts by mass, and even more preferably 0.05 to 2 parts by mass, relative to 100 parts by mass of the hydrogenated block copolymer.

[0281] In addition, during polymerization, a monomer having a reactive functional group (e.g., one or more functional groups selected from an alkoxysilyl group, a carboxyl group, an amino group, a hydroxyl group, an epoxy group, a group derived from an acid anhydride, an ester group, a mercapto group, and an oxazoline group) and a monomer not having the above-mentioned reactive functional group can be copolymerized to produce the thermoplastic resin (B). As the monomer having a reactive functional group, maleic anhydride, glycidyl methacrylate, 2-isopropenyl-2-oxazoline, etc. can be cited.

[0282] <Method for producing resin composition>

[0283] The resin composition can be produced by preparing a mixture of a thermoplastic resin (A) and a thermoplastic resin (B) in a molten state, and mixing the mixture with a polar resin (C). The core-shell structure can be easily formed by melt-kneading the thermoplastic resin (A), the thermoplastic resin (B) having a reactive functional group, and the polar resin (C).

[0284] The process for preparing the mixture is not particularly limited, and it can be prepared, for example, using a mixing device. As a mixing device, a method generally used in the art can be adopted. The components can be mixed using a mixer such as a Henschel mixer, a V blender, a ribbon blender, a drum blender, a cone blender, or after mixing, they can be mixed by a single screw or twin screw extruder, a kneader, etc. The temperature during melt mixing can be appropriately set, usually 150 to 300° C., preferably 160 to 250° C.

[0285] One embodiment of a method for producing a resin composition comprises the steps of adding a free radical initiator in a molten state to a mixture of a thermoplastic resin (A) and a precursor (B0) of a thermoplastic resin (B) satisfying the following conditions (4) and (5), thereby introducing a reactive functional group into the precursor (B0) to obtain the thermoplastic resin (A) and the thermoplastic resin (B) having a reactive functional group.

[0286] (4) The thermoplastic resin (A) is a block copolymer having a block (A-1) containing more than 70 mol % of aromatic vinyl monomer units and a block (A-2) containing more than 30 mol % of conjugated diene monomers, or a hydrogenated product thereof, and has a glass transition temperature in the range of -30 to +50°C.

[0287] (5) The glass transition temperature of the precursor (B0) of the thermoplastic resin (B) is within the range of -100 to -31°C.

[0288] A free radical initiator is added in advance to a mixture of a thermoplastic resin (A) and a precursor (B0) of a thermoplastic resin (B) in a molten state to introduce a reactive functional group into the precursor (B0), thereby obtaining a thermoplastic resin (A) and a thermoplastic resin (B) having a reactive functional group.

[0289] In this way, the step of preparing a thermoplastic resin (B) into which a reactive functional group has been introduced in advance can be omitted, and a kneaded product of the thermoplastic resin (A) and the thermoplastic resin (B) can be obtained while introducing the reactive functional group into the precursor (B0), thereby simplifying the production steps.

[0290] Furthermore, by using a thermoplastic resin (A) having a glass transition temperature within the above numerical range, introduction of reactive functional groups into the thermoplastic resin (B) is promoted, and a large amount of reactive functional groups can be introduced into the thermoplastic resin (B).

[0291] In one embodiment of the method for producing a resin composition of the present invention, the thermoplastic resin (A) is a hydrogenated product of a block copolymer having a block (A-1) and a block (A-2), and the hydrogenation rate of the hydrogenated product is 50 to 99 mol %.

[0292] In one embodiment of the method for producing a resin composition of the present invention, the thermoplastic resin (A) has a structure of an alicyclic skeleton represented by the above formula (X) or a hydrogenated product thereof.

[0293] In one embodiment of the method for producing a resin composition of the present invention, the reactive functional group of the thermoplastic resin (B) is one or more functional groups selected from an alkoxysilyl group, an epoxy group, and a group derived from an acid anhydride.

[0294] The obtained resin composition can be made into an appropriate form according to the purpose, the mode of use, etc., and can be made into, for example, a pellet form, a flake form, or a pellet form.

[0295] <Method for producing resin modifier>

[0296] It should be noted that the step of adding a free radical initiator in a molten state to a mixture of a thermoplastic resin (A) and a precursor (B0) of a thermoplastic resin (B) satisfying the above conditions (4) and (5) to introduce a reactive functional group into the precursor (B0) to obtain a thermoplastic resin (A) and a thermoplastic resin (B) having a reactive functional group, and the method for producing a resin composition comprising the above steps can also be said to be a method for producing a resin modifier comprising the thermoplastic resin (A) and the resin composition (B). The resin modifier makes the processability, moldability, mechanical properties, etc. of the polar resin (C) excellent.

[0297] [Characteristics of resin composition]

[0298] <Volume average dispersion diameter>

[0299] In the molded article of the resin composition of the present embodiment, the volume average dispersion diameter of the core-shell structure can be set to 0.01 to 10 μm, 0.03 to 8 μm, and further 0.05 to 6 μm. By making the volume average dispersion diameter of the core-shell structure within the above numerical range, the dispersibility of the core-shell structure in the polar resin (C) can be improved, and the mechanical strength of the resin composition can be improved.

[0300] The volume average dispersion diameter of the core-shell structure is obtained by freeze-fracture of the test piece using liquid nitrogen, etching the cross section, and observing the sample with platinum or the like deposited thereon with a SEM. In the obtained image, the average value of the diameters of 50 pores opened by etching can be calculated as the average dispersion diameter. Specifically, it is a value measured according to the process described in the examples.

[0301] <IZOD impact strength>

[0302] The resin composition of the present embodiment has excellent impact resistance, and for example, the IZOD impact strength can be 5 [J / m] or more, 10 [J / m] or more, and further 15 [J / m] or more.

[0303] The IZOD impact strength is measured in accordance with JIS K 7110 by storing the prepared test piece at 23° C. for at least 16 hours using an impact strength tester.

[0304] <Loss coefficient>

[0305] The resin composition of the present embodiment can show good vibration damping properties in a wide temperature range.

[0306] The good vibration damping properties in a wide temperature range exhibited by the resin composition of the present embodiment can be achieved by appropriately controlling the selection of monomers used in the aforementioned block copolymers, hydrogenated block copolymers, and their modified products (modified block copolymers, modified hydrogenated products), the balance between the amount of vinyl bonds and the hydrogenation rate, the production methods of the block copolymers, hydrogenated block copolymers, and their modified products, and other constituent elements of the block copolymers, hydrogenated block copolymers, and their modified products, and also by the combination of the block copolymers, hydrogenated block copolymers, and their modified products used in the resin composition with the resin, and the content ratio thereof.

[0307] For example, the vibration damping property can be evaluated as follows by measuring the loss coefficient of a test piece having a length of 200 mm, a width of 10 mm, and a thickness of 2 mm and performing an oscillation test using a central vibration method according to JIS K 7391 (2008).

[0308] The loss coefficient at a frequency of 300 Hz and a temperature of 0° C. is preferably 0.008 or more. Furthermore, the loss coefficient can be 0.020 or more, or 0.030 or more.

[0309] The loss coefficient at a frequency of 300 Hz and a temperature of 10° C. is preferably 0.008 or more. Furthermore, the loss coefficient can be 0.020 or more, or 0.030 or more.

[0310] The loss coefficient at a frequency of 300 Hz and a temperature of 20° C. is preferably 0.008 or more. Furthermore, the loss coefficient can be 0.020 or more, or 0.030 or more.

[0311] The loss coefficient at a frequency of 300 Hz and a temperature of 30° C. is preferably 0.008 or more. Furthermore, the loss coefficient can be 0.020 or more, or 0.030 or more.

[0312] The loss coefficient at a frequency of 300 Hz and a temperature of 40° C. is preferably 0.008 or more. Furthermore, the loss coefficient can be 0.020 or more, or 0.030 or more.

[0313] The loss coefficient at a frequency of 300 Hz and a temperature of 60° C. is preferably 0.008 or more. Furthermore, the loss coefficient can be 0.020 or more, or 0.030 or more.

[0314] The loss coefficient at a frequency of 300 Hz and a temperature of 80° C. is preferably 0.008 or more. Furthermore, the loss coefficient can be 0.020 or more, or 0.030 or more.

[0315] The loss coefficient at a frequency of 300 Hz and a temperature of 100° C. is preferably 0.008 or more. Furthermore, the loss coefficient can be 0.020 or more, or 0.030 or more.

[0316] [use]

[0317] The above-mentioned resin composition can be used for various purposes.

[0318] The resin composition of this embodiment has excellent vibration damping properties and can be used for various applications. Therefore, the present invention also provides vibration damping materials, films or sheets, adhesives or bonding agents, etc. using the resin composition or resin modifier of the present invention.

[0319] In addition, a laminate having an X layer obtained by containing the resin composition or resin modifier according to the present invention and a Y layer laminated on at least one surface of the X layer can also be provided. The laminate is suitable for, for example, laminated glass, and by making the X layer as an intermediate film for laminated glass and the Y layer as glass, not only excellent vibration damping properties but also excellent sound insulation properties can be expected.

[0320] In addition, as the Y layer, in addition to the above-mentioned glass layer, any layer may be appropriately selected according to various uses, and examples thereof include a layer containing a thermoplastic resin other than the thermoplastic resin used in the resin composition or resin modifier involved in the present invention, etc. Examples of the thermoplastic resin include polyvinyl acetal resin, ionomer, ethylene-vinyl acetate copolymer, urethane resin, polyamide resin, etc.

[0321] As other uses, granules, veils, sound absorbing materials, sound insulating materials, rubber dams, sole materials, floor materials, weather stripping, floor mats, front panel insulators, ceiling linings, door panels, hood covers, door hole seals, fender linings, etc. can be mentioned, and they are also useful in these uses.

[0322] In addition, the resin composition or resin modifier of the present invention can also be used for various automotive components in the automotive field, such as cooling parts such as thermostat housings, radiator tanks, radiator hoses, water outlets, water pump housings, and rear joints; intake and exhaust system parts such as intercooler tanks, intercooler housings, turbine duct pumps, EGR cooler housings, resonators, throttle bodies, intake manifolds, and exhaust pipes; fuel delivery pumps, gasoline tanks, quick connectors, carbon canisters, pump modules, fuel piping, fuel filters, lock nuts, sealing materials, and other fuel system parts; suspension brackets, torque rods, cylinder head covers, and other structural parts; drive systems such as bearing retainers, gear tensioners, headlight actuator gears, HVAC gears, sliding door rollers, and clutch peripheral parts Components; pneumatic brake pipes and other brake system components; wiring harness connectors, motor components, sensors, ABS spools, combination switches, on-board switches, electronic control unit (ECU) boxes and other on-board electrical components in the engine compartment; sliding door shock absorbers, door mirror brackets, door mirror brackets, interior mirror brackets, roof rails, engine suspension brackets, air purifier intake pumps, door limiters, plastic chains, car logos, grabbers, brake covers, cup holders, air bags, fenders, spoilers, radiator supports, radiator racks, shutters, air scoops, hood bulges, trunk doors, fuel feeder modules, floor mats, instrument panels, dashboards, front bulkhead insulators, rubber dams, weather stripping, tires and other interior and exterior components, etc.

[0323] In addition, it can be used in the field of home appliances for various video recorders such as televisions, Blu-ray recorders, HDD recorders, projectors, game consoles, digital cameras, home video cameras, antennas, speakers, electronic dictionaries, IC recorders, FAX, copiers, telephones, doorbells, rice cookers, microwave ovens, ovens, refrigerators, dishwashers, dish dryers, IH cooking heaters, hot plates, vacuum cleaners, washing machines, chargers, sewing machines, irons, dryers, electric bicycles, air purifiers, water purifiers, electric toothbrushes, lighting fixtures, air conditioners, outdoor units of air conditioners, dehumidifiers, humidifiers, and other electrical products as sealing materials, adhesives, binders, seals, O-rings, belts, soundproofing materials, etc. It can also be used as fibers. Example

[0324] Hereinafter, the present invention will be specifically described by way of Examples and Comparative Examples, but the present invention is not limited thereto.

[0325] The methods for evaluating the physical properties of the hydrogenated block copolymers obtained in the Production Examples described below are described below.

[0326] (1) Content of polymer block (A-1)

[0327] The block copolymer before hydrogenation was dissolved in CDCl3. 1The content of the polymer block (A-1) was calculated from the ratio of the peak intensity derived from styrene to the peak intensity derived from diene by H-NMR measurement [apparatus: "ADVANCE 400 Nano bay" (manufactured by Bruker Corporation), measurement temperature: 30°C].

[0328] (2) Weight average molecular weight (Mw)

[0329] The polystyrene-equivalent weight average molecular weight (Mw) of the block copolymer or the hydrogenated product was determined by gel permeation chromatography (GPC) measurement under the following conditions.

[0330] (GPC measurement apparatus and measurement conditions)

[0331] · Apparatus: GPC apparatus "HLC-8020" (manufactured by Tosoh Corporation)

[0332] Separation columns: "TSKgel GMHXL", "G4000HXL" and "G5000HXL" manufactured by Tosoh Corporation were connected in series.

[0333] ·Eluent: Tetrahydrofuran

[0334] Eluent flow rate: 0.7mL / min

[0335] Sample concentration: 5mg / 10mL

[0336] Column temperature: 40°C

[0337] Detector: Differential refractive index (RI) detector

[0338] ·Standard curve: Prepared using standard polystyrene.

[0339] (3) Hydrogenation rate in polymer block (A-2)

[0340] pass 1 The H-NMR measurement was calculated from the ratio of the peak area of ​​residual olefins derived from isoprene and / or butadiene to the peak area derived from ethylene, propylene and / or butene.

[0341] · Equipment: Nuclear magnetic resonance device "ADVANCE 400 Nano bay" (manufactured by Bruker)

[0342] Solvent: CDCl3.

[0343] (4) Vinyl bond content in polymer block (A-2)

[0344] The block copolymer before hydrogenation was dissolved in CDCl3. 1H-NMR measurement [apparatus: "ADVANCE 400Nano bay" (manufactured by Bruker Corporation), measurement temperature: 30°C]. The vinyl bond content (the total content of the 3,4-bonded unit and the 1,2-bonded unit) was calculated from the ratio of the total peak area of ​​the structural units derived from isoprene and / or butadiene to the peak area corresponding to the 3,4-bonded unit and the 1,2-bonded unit in the isoprene structural unit, the 1,2-bonded unit in the butadiene structural unit, or the structural unit derived from a mixture of isoprene and butadiene, respectively.

[0345] (5) Content of the alicyclic skeleton (X) in the polymer block (A-2)

[0346] 600 mg of the block copolymer before hydrogenation and 340 mg of Cr(acac) were dissolved in 34 mL of CDCl and quantified using a 10 mm NMR tube. 13 C-NMR measurement (pulse program: zgig, inverse gated 1H decoupling method) [apparatus: "ADVANCE 400 Nano bay" (manufactured by Bruker), measurement temperature: 30°C] was performed to calculate the contents of the alicyclic skeletons X, X1, and X2 in the polymer block (A-2) by the following method.

[0347] In addition, in Table 1, X, X1, and X2 represent the following alicyclic skeletons.

[0348] X: an alicyclic skeleton having a combination of the following substituents (i) to (vi):

[0349] X1: an alicyclic skeleton having a combination of the following substituents (i) and (iv):

[0350] X2: an alicyclic skeleton having a combination of the following substituents (ii), (iii), (v), and (iv):

[0351] (i):R 1 = hydrogen atom, R 2 = hydrogen atom, R 3 =Hydrogen atom; (1,2Bd+Bd)

[0352] (ii):R 1 = hydrogen atom, R 2 =Methyl, R 3 = Hydrogen atom; (1,2Bd+1,2Ip)

[0353] (iii):R 1 = hydrogen atom, R 2 = hydrogen atom, R 3= methyl; (1,2Bd+3,4Ip)

[0354] (iv):R 1 =Methyl, R 2 = hydrogen atom, R 3 =Hydrogen atom; (1,2Ip+Bd)

[0355] (v):R 1 =Methyl, R 2 =Methyl, R 3 = Hydrogen atom; (1,2Ip+1,2Ip)

[0356] (vi):R 1 =Methyl, R 2 = hydrogen atom, R 3 = methyl; (1,2Ip+3,4Ip)

[0357] In addition, Ip represents isoprene, and Bd represents butadiene.

[0358] [Calculation method]

[0359] The structures derived from each peak are shown in Table 1-1. If the integral values ​​of each peak are recorded as a to g, the integral values ​​of each structure are as shown in Table 1-2, and the contents of X, X1, and X2 are calculated by (a+gc) / (a+b+c-d+e / 2+2f), (gc) / (a+b+c-d+e / 2+2f), and a / (a+b+c-d+e / 2+2f).

[0360] [Table 1]

[0361] .

[0362] (6) 13 C-NMR peak area ratio

[0363] The above quantitative analysis was performed on the hydrides of Preparation Examples 1 to 5. 13 C-NMR measurement [apparatus: "ADVANCE 400 Nanobay" (manufactured by Bruker), measurement temperature: 30°C, solvent: CDCl3], and the peak area ratio [peak area of ​​chemical shift values ​​50.0 to 52.0 ppm] / [peak area of ​​chemical shift values ​​43.0 to 45.0 ppm] was calculated.

[0364] (7) tanδ peak temperature, peak intensity, maximum width of the temperature region where tanδ reaches 1.0 or above, and tanδ intensity at 20°C and 30°C

[0365] For the following measurement, a hydrogenated block copolymer was pressed at a temperature of 230° C. and a pressure of 10 MPa for 3 minutes to prepare a single-layer sheet having a thickness of 1.0 mm. The single-layer sheet was cut into a disk shape to prepare a test sheet.

[0366] In the measurement, a strain-controlled dynamic viscoelasticity apparatus “ARES-G2” (manufactured by Thei Instruments Japan Co., Ltd.) having a circular plate diameter of 8 mm was used as a parallel plate vibration rheometer in accordance with JIS K 7244-10 (2005).

[0367] The gap between the two flat plates is completely filled with the test sheet, and the test sheet is vibrated at a frequency of 1 Hz with a strain of 0.1%, and the temperature is raised from -70°C to +100°C at a constant rate of 3°C / min. The temperature of the test sheet and the circular plate is maintained until there is no change in the measured values ​​of the shear loss modulus and the shear storage modulus, and the maximum value of the peak intensity of tanδ (peak intensity) and the temperature at which the maximum value is obtained (peak temperature) are calculated. In addition, the maximum width of the temperature region where tanδ reaches 1.0 or more, and the tanδ intensity at 20°C and 30°C are calculated. The larger the value, the better the shock absorption.

[0368] (8) Glass transition temperature and melting point of resin

[0369] The glass transition temperature and melting point of the resin were measured using a DSC measuring device (DSC6200 manufactured by Hitachi HiTech Science Co., Ltd.) in a temperature range of -100°C to +350°C and a heating rate of 20°C / min. The temperature of the inflection point of the baseline shift due to the glass transition was recorded as the glass transition point, and the temperature at the position where the endothermic peak reached the peak value was recorded as the melting point. It should be noted that at least one of the glass transition temperature and melting point of nylon 6, PBT, and POM described later was confirmed to be 80°C or higher in any of the resins.

[0370] [Production Example 1]

[0371] Production of hydrogenated block copolymer (TPE-1)

[0372] Into a nitrogen-purged and dried pressure vessel, 50 kg of cyclohexane as a solvent and 76 g of a 10.5 mass % cyclohexane solution of sec-butyllithium as an anionic polymerization initiator (substantially 8.0 g of sec-butyllithium added) were added.

[0373] After the temperature in the pressure vessel was raised to 50°C, 1.0 kg of styrene (1) was added and polymerization was carried out for 1 hour. At the temperature in the vessel of 50°C, 63 g of 2,2-di(2-tetrahydrofuryl)propane (DTHFP) as a Lewis base was added. A mixed liquid of 8.16 kg of isoprene and 6.48 kg of butadiene was added over 5 hours at the average diene feed rate shown in Table 2. The mixture was polymerized for 2 hours. Further, 1.0 kg of styrene (2) was added and polymerization was carried out for 1 hour. Thus, a reaction liquid containing a polystyrene-poly(isoprene / butadiene)-polystyrene triblock copolymer was obtained.

[0374] To the reaction solution, a Ziegler hydrogenation catalyst composed of nickel octoate and trimethylaluminum was added under hydrogen gas pressure, and the reaction was carried out for 5 hours under the conditions of a hydrogen pressure of 1 MPa and 80° C. The reaction solution was allowed to cool and depressurized, and then the catalyst was removed by washing with water and vacuum dried to obtain a hydrogenated product of a polystyrene-poly(isoprene / butadiene)-polystyrene triblock copolymer (hereinafter referred to as TPE-1).

[0375] The raw materials and the amounts used are shown in Table 2. Table 3 also shows the results of the above-mentioned physical property evaluations.

[0376] [Production Example 2]

[0377] Production of hydrogenated block copolymer (TPE-2)

[0378] The hydrogenated product of polystyrene-polyisoprene-polystyrene triblock copolymer (hereinafter referred to as TPE-2) was obtained in the same manner as in Production Example 1 except that the components, their amounts used, and reaction conditions were changed as shown in Table 2. In addition, the results of the above-mentioned physical property evaluations are shown in Table 3.

[0379] [Production Example 3]

[0380] Production of hydrogenated block copolymer (TPE-3)

[0381] Each component, its usage, and reaction conditions were changed as shown in Table 2. A hydrogenated product of a polystyrene-polybutadiene-polystyrene triblock copolymer (hereinafter referred to as TPE-3) was obtained in the same manner as in Production Example 1. In addition, the results of the above-mentioned physical property evaluations are shown in Table 3.

[0382] [Production Example 4]

[0383] Production of hydrogenated block copolymer (TPE-4)

[0384] The hydrogenated product of polystyrene-polyisoprene-polystyrene triblock copolymer (hereinafter referred to as TPE-4) was obtained in the same manner as in Production Example 1 except that the components, their amounts used, and reaction conditions were changed as shown in Table 2. In addition, the results of the above-mentioned physical property evaluations are shown in Table 3.

[0385] [Production Example 5]

[0386] Production of hydrogenated block copolymer (TPE-5)

[0387] The hydrogenated product of polystyrene-polyisoprene-polystyrene triblock copolymer (hereinafter referred to as TPE-5) was obtained in the same manner as in Production Example 1 except that the components, their amounts used, and reaction conditions were changed as shown in Table 2. In addition, the results of the above-mentioned physical property evaluations are shown in Table 3.

[0388] [Table 2]

[0389] .

[0390] [Table 3]

[0391] .

[0392] The hydrogenated block copolymers of Manufacturing Examples 1, 2, 4, and 5 show a peak intensity of tan δ of 1.0 or more. In addition, the temperature range of tan δ ≥ 1.0 is wide, so it can be said that it is suitable for a wide range of uses as a shock absorbing material. In particular, if compared with Manufacturing Example 3, in Manufacturing Examples 1, 2, 4, and 5, the tan δ intensity at 20°C and 30°C is high, it can be seen that the shock absorbing property near room temperature is excellent. In particular, the tan δ intensity at 20°C and 30°C of the hydrogenated block copolymers of Manufacturing Examples 1, 2, and 4 shows a higher value, and it can be seen that the shock absorbing property near room temperature is more excellent. In addition, the peak temperature of tan δ of the hydrogenated block copolymer of Manufacturing Example 5 is high, and it can be seen that the shock absorbing property at high temperature is excellent.

[0393] <Production of modified hydride>

[0394] (Modified TPE-1)

[0395] As the modified hydrogenated product, Teflon MH5020 manufactured by Mitsui Chemicals, Inc., which is a maleic anhydride-modified ethylene / butene copolymer, was used. This was referred to as modified TPE-1. The amount of maleic anhydride modification in modified TPE-1 was 1.0 phr.

[0396] (Modified TPE-2)

[0397] The hydrogenated product TPE-3 obtained above was modified with maleic anhydride by the following process, thereby obtaining a modified hydrogenated product (modified TPE-2) having a maleic anhydride modification amount of 0.6 phr.

[0398] Using a twin-screw extruder "ZSK26mc" (26 mmφ, L / D=56) manufactured by Coperion, 10 kg of the hydrogenated block copolymer TPE-3 obtained above was taken out and made into a molten state under the following extrusion conditions, and 0.01 kg of 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane (パーヘキサ25B-40, manufactured by NOF Corporation) as a free radical initiator and 0.1 kg of maleic anhydride as a modifier were added to carry out a modification reaction to obtain a modified hydrogenated product.

[0399] 〈Extrusion conditions〉

[0400] Twin-screw extruder temperature settings: resin feed port 40°C, barrel inlet 150°C, adapter 210°C, die head 210°C

[0401] Screw speed: 300rpm.

[0402] (Modified TPE-3)

[0403] A modified hydrogenated product having a maleic anhydride modification amount of 2.1 phr was obtained by the same procedure as in the preparation of modified TPE-2 except that the radical initiator was changed to 0.03 kg and the maleic anhydride was changed to 0.3 kg.

[0404] (Modified TPE-4)

[0405] As modified TPE-4, EPOPRENE AT501 manufactured by DICEL CORPORATION, which is an epoxide of a styrene-butadiene block copolymer, was used.

[0406] (Modified TPE-5)

[0407] A modified hydride having a maleic anhydride modification amount of 0.7 phr was obtained by the same procedure as in the preparation of modified TPE-2 except that TPE-1 was used as the hydride and the amount of the radical initiator was changed to 0.05 kg.

[0408] <Resin composition>

[0409] [Examples 1 to 10] [Comparative Examples 1 and 2]

[0410] The hydrogenated block copolymers TPE-1 and TPE-2 obtained above, the modified products of the hydrogenated block copolymers (modified TPE-1 to modified TPE-3), modified polyethylene wax-1, modified polyethylene wax-2, and nylon 6 (UBE nylon 1013B manufactured by Ube Industries, Ltd.) were melt-kneaded using a twin-screw extruder "ZSK26mc" (26 mmφ, L / D=56) manufactured by Coperion under the following extrusion conditions to prepare resin compositions of Examples 1 to 10 and Comparative Examples 1 and 2. In addition, except for Examples 3, 8 to 10 and Comparative Examples 1 and 2, the components other than nylon 6 were pre-kneaded using the above-mentioned apparatus under the following pre-kneading conditions, and the obtained compositions were melt-kneaded with nylon 6. The melting point of nylon 6 is 215-225°C.

[0411] 〈Extrusion conditions〉

[0412] Twin-screw extruder temperature settings: resin feed port 40°C, barrel inlet 250°C, adapter 250°C, die head 250°C

[0413] Screw speed: 300rpm.

[0414] 〈Pre-mixing conditions〉

[0415] Twin-screw extruder temperature settings: resin feed port 40°C, barrel inlet 180°C, adapter 210°C, die head 210°C

[0416] Screw speed: 300rpm.

[0417] As modified polyethylene wax-1, HiWax 2203A (acid-modified type, acid value 30 mgKOH / g) manufactured by Mitsui Chemicals, Inc. was used. As modified polyethylene wax-2, HiWax 4202E (oxidized type, acid value 17 mgKOH / g) manufactured by Mitsui Chemicals, Inc. was used.

[0418] The above-mentioned TPE-1 and TPE-2 correspond to the thermoplastic resin (A), the modified TPE-1 to modified TPE-3, the modified polyethylene wax-1 and the modified polyethylene wax-2 correspond to the thermoplastic resin (B), and nylon 6 corresponds to the polar resin (C).

[0419] The measurement results are shown in the following Table 4. In addition, in Table 4, for reference, measurement data of the case where only nylon 6 was used is also recorded as Reference Example 1. In Table 4, the case where pre-mixing of components other than nylon 6 was performed is indicated by "Y", and the case where it was not performed is indicated by "-".

[0420] [Examples 11 to 17] [Comparative Example 3]

[0421] The hydrogenated block copolymers TPE-1 and TPE-4 obtained above, the modified TPE-1, modified TPE-3 and modified TPE-4 obtained above as modified products of the hydrogenated block copolymers, modified resin-1 and modified resin-2, and a polybutylene terephthalate resin (Toray Corporation Toray 1401X31) as a thermoplastic resin were melt-kneaded using a twin-screw extruder "ZSK26mc" (26 mmφ, L / D=56) manufactured by Coperion under the following extrusion conditions to prepare resin compositions of Examples 11 to 17 and Comparative Example 3 according to the proportions shown in Table 5. The melting point of the polybutylene terephthalate resin is 225°C.

[0422] 〈Extrusion conditions〉

[0423] Twin-screw extruder temperature settings: resin feed port 40°C, barrel inlet 250°C, adapter 250°C, die head 250°C

[0424] Screw speed: 300rpm.

[0425] It should be noted that as the polybutylene terephthalate resin, Toray Co., Ltd. ...

[0426] The measurement results are shown in the following Table 5. In Table 5, the polybutylene terephthalate resin is abbreviated as "PBT". The above-mentioned TPE-1 and TPE-4 correspond to thermoplastic resin (A), modified TPE-1, modified TPE-3, modified TPE-4, modified resin-1 and modified resin-2 correspond to thermoplastic resin (B), and PBT corresponds to polar resin (C). In Table 5, for reference, as Reference Example 2, measurement data of the case where only PBT was used are also described.

[0427] [Examples 18 and 19] [Comparative Example 4]

[0428] The hydrogenated block copolymer TPE-1 obtained above, Polyplastics Corporation Diuracon (registered trademark) M90-44 as a polyacetal resin, BASF Elastollan C80A as a thermoplastic polyurethane elastomer, and Kurara TU polymer S5265 as a block copolymer obtained by bonding a styrene elastomer to one polyurethane elastomer block were melt-kneaded using a twin-screw extruder "ZSK26mc" (26 mmφ, L / D=56) manufactured by Coperion under the following extrusion conditions to prepare resin compositions of Examples 18 and 19 and Comparative Example 4. It should be noted that the melting point of the polyacetal resin is 165°C.

[0429] 〈Extrusion conditions〉

[0430] Twin-screw extruder temperature settings: resin feed port 40°C, barrel inlet 200°C, adapter 200°C, die head 200°C

[0431] Screw speed: 300rpm.

[0432] In addition, as the polyacetal resin, Duracon (registered trademark) M90-44 manufactured by Polyplastics Corporation was used.

[0433] The measurement results are shown in the following Table 6. In Table 6, the above-mentioned Diuracon M90-44 is abbreviated as "POM", Elastollan C80A is abbreviated as "TPU-1", and S5265 is abbreviated as "TPU-2". The above-mentioned TPE-1 corresponds to the thermoplastic resin (A), TPU-1 and TPU-2 correspond to the thermoplastic resin (B), and POM corresponds to the polar resin (C). In Table 6, for reference, as Reference Example 3, the measurement data of the case where only POM is used is also recorded.

[0434] [Examples 20 to 23]

[0435] According to the ratio shown in Table 7, the hydrogenated block copolymer TPE-1, modified TPE-4, modified resin-1 and modified resin-2, and polyester thermoplastic elastomer (hereinafter referred to as TPEE) obtained above were melt-kneaded using a twin-screw extruder "ZSK26mc" (26 mmφ, L / D=56) manufactured by Coperion under the following extrusion conditions to prepare the resin compositions of Examples 20 to 23.

[0436] 〈Extrusion conditions〉

[0437] Twin-screw extruder temperature settings: resin feed port 40°C, barrel inlet 200°C, adapter 200°C, die head 200°C

[0438] Screw speed: 300rpm.

[0439] As TPEE, Hitrel 3046 (registered trademark) manufactured by Toray Dupon Co., Ltd. was used. As modified resin-1, modified resin-2, and modified TPE-4, the same ones as shown in Table 5 were used.

[0440] The measurement results are shown in the following Table 7. The above-mentioned TPE-1 corresponds to the thermoplastic resin (A), the modified resin-1, the modified resin-2 and the modified TPE-4 correspond to the thermoplastic resin (B), and the TPEE corresponds to the polar resin (C). In Table 7, for reference, as Reference Example 4, the measurement data of the case where only TPEE was used is also recorded.

[0441] [Examples 24 to 29] [Comparative Example 5]

[0442] According to the ratio shown in Table 8, the hydrogenated block copolymers TPE-1, TPE-2 and TPE-5 obtained above, the modified TPE-2 and modified TPE-5 obtained above, modified polypropylene (modified PP), glass fiber, nylon 6, and modified polyethylene wax-1 were melt-kneaded using a twin-screw extruder "ZSK26mc" (26 mmφ, L / D=56) manufactured by Coperion under the following extrusion conditions to prepare the resin compositions of Examples 24 to 29 and Comparative Example 5.

[0443] 〈Extrusion conditions〉

[0444] Twin-screw extruder temperature settings: resin feed port 40°C, barrel inlet 250°C, adapter 250°C, die head 250°C

[0445] Screw speed: 300rpm.

[0446] It should be noted that as nylon 6, UBE nylon 1013B manufactured by Ube Industries, Ltd. was used. In addition, as glass fiber, Chip Soft T-251H manufactured by Nippon Electric Glass Co., Ltd. was used. As modified polyethylene wax-1, the same one as shown in Table 4 was used. As modified PP, Adma QE840 manufactured by Mitsui Chemicals, Inc. was used.

[0447] The measurement results are shown in the following Table 8. The above-mentioned TPE-1, TPE-2 and TPE-5 correspond to thermoplastic resin (A), modified TPE-2, modified TPE-5, modified PP and modified polyethylene wax-1 correspond to thermoplastic resin (B), nylon 6 corresponds to polar resin (C), and glass fiber corresponds to additive. In Table 8, for reference, as Reference Example 5, measurement data of the case where only nylon 6 and glass fiber were used are also recorded.

[0448] [Examples 30 to 32] [Comparative Example 6]

[0449] According to the ratio shown in Table 9, PPS resin, hydrogenated block copolymers TPE-1 and TPE-2 obtained above, modified resin-3, and modified resin-4 were melt-kneaded under the following extrusion conditions using a twin-screw extruder "ZSK26mc" (26mmφ, L / D=56) manufactured by Coperion, thereby preparing the resin compositions of Examples 30 to 32 and Comparative Example 6.

[0450] 〈Extrusion conditions〉

[0451] Twin-screw extruder temperature settings: resin feed port 40°C, barrel inlet 280°C, adapter 300°C, die head 300°C

[0452] Screw speed: 300rpm.

[0453] It should be noted that as the PPS resin, Toray Corporation's Toray A900 was used. In addition, as modified resin-3, epoxy-containing acrylic styrene polymer "Macpulf G-0130SP" manufactured by NOF Corporation was used. As modified resin-4, styrene-2-isopropenyl-2-oxazoline copolymer "Epocros RPS-1005" manufactured by Nippon Catalyst Co., Ltd. was used.

[0454] The measurement results are shown in the following Table 9. The above-mentioned TPE-1 and TPE-2 correspond to the thermoplastic resin (A), the modified resin-3 and the modified resin-4 correspond to the thermoplastic resin (B), and the PPS resin corresponds to the polar resin (C). In Table 9, for reference, as Reference Example 6, the measurement data of the case where only the PPS resin is used is also recorded.

[0455] [Physical property evaluation]

[0456] The physical properties of the resin compositions prepared above are evaluated as follows. It should be noted that the IZOD impact strength was measured for Examples 1 to 10, Comparative Examples 1 and 2, and Reference Example 1. It should be noted that the volume average dispersion diameter was not measured for the molded products in which the core-shell structure was not observed.

[0457] (Loss coefficient at 0℃, 10℃, 20℃, 40℃, 60℃, 80℃, 100℃)

[0458] The obtained resin composition was injection molded by an injection molding machine ("EC75SX", manufactured by Toshiba Machine Co., Ltd.) to produce a sheet of 200 mm in length × 40 mm in width × 2 mm in thickness. The sheet was cut into pieces of 200 mm in length × 10 mm in width × 2 mm in thickness, and a contact chip was bonded to the center using an adhesive containing α-cyanoacrylate as the main component to produce a sample.

[0459] Next, the sample was mounted on a loss coefficient measurement system (exciter model 4809 and impedance head model 80001, manufactured by Burleigh Corporation).

[0460] A contact chip bonded to the center of the sample is installed at the front end of the vibration force detector built into the impedance head. Vibration is applied to the center of the laminate in the frequency range of 0 to 8,000 Hz. By detecting the vibration force and acceleration waveform at this point, an oscillation test using the central vibration method in accordance with JIS K 7391 (2008) is performed to detect the vibration force at the center and the acceleration signal representing the acceleration waveform. The samples are measured at temperatures of 0°C, 10°C, 20°C, 40°C, 60°C, 80°C, and 100°C.

[0461] Based on the obtained vibration force and the velocity signal obtained by integrating the acceleration signal, the mechanical impedance of the vibration point (the center of the sample to which vibration is applied) is obtained. In addition, the horizontal axis is represented as the frequency, and the vertical axis is represented as the above mechanical impedance. The obtained impedance curve is prepared, and the loss coefficient of the sample at each temperature is obtained from the half-width of the second peak (2nd mode) from the low frequency side.

[0462] It should be noted that the larger the loss coefficient value, the higher the vibration reduction effect. The results are shown in Tables 4 to 9.

[0463] (Volume average dispersion diameter)

[0464] The above-mentioned test piece used in the determination of the loss coefficient was freeze-fractured using liquid nitrogen, and the cross section was etched with xylene to prepare a sample deposited with platinum and observed with SEM. In the obtained image, the average value of the diameters of 50 pores opened by etching was used as the average dispersion diameter. The results are shown in Tables 4 to 9. It should be noted that when the pores are flat shapes such as ellipses, the average value of the major axis length is used as the volume average dispersion diameter.

[0465] (Formation of core-shell structure)

[0466] The obtained resin composition was injection molded by an injection molding machine ("EC75SX", manufactured by Toshiba Machine Co., Ltd.) to produce a sheet of 200 mm in length × 40 mm in width × 2 mm in thickness. The sheet was cut into a length of 200 mm × a width of 10 mm × a thickness of 2 mm to make a test piece. The cross section of the test piece was observed with a transmission electron microscope (TEM), and the core-shell structure in which any one of modified TPE-1 to modified TPE-5, modified polyethylene wax -1 to modified polyethylene wax -2, modified resin -1 to modified resin -4, TPU-1 to TPU-2, and modified PP was observed as a shell, and at least one of the hydride TPE-1 to TPE-5 was a core was recorded as "Y", and if the above structure was not observed, it was recorded as "-". It should be noted that the test piece was embedded in epoxy resin after cutting, and ultrathin sections were cut into about 100 μm, and stained with ruthenium tetroxide for cross-sectional observation. The results are shown in Tables 4 to 9. The enlarged cross-sectional photographs of Example 6 observed using TEM are shown in Figure 2 The enlarged cross-sectional photograph of Example 2 is shown in Figure 4 .

[0467] (Appearance of molded product)

[0468] The obtained resin composition was injection molded by an injection molding machine ("EC75SX", manufactured by Toshiba Machine Co., Ltd.) to produce a sheet of 200 mm in length × 40 mm in width × 2 mm in thickness. The sheet was cut into pieces of 200 mm in length × 10 mm in width × 2 mm in thickness to produce a molded product. The appearance of the molded product was visually confirmed, and the case of poor appearance such as surface peeling was recorded as "C", and otherwise recorded as "A". The results are shown in Tables 4 to 6 and 8.

[0469] (IZOD impact strength)

[0470] The obtained resin composition was injection molded into a size of 10 mm in length × 80 mm in width × 4 mm in thickness by an injection molding machine ("EC75SX", manufactured by Toshiba Machine Co., Ltd.), and cut by notching according to JIS K 7110 to prepare a test piece. After the test piece was stored at 23°C for 16 hours, the IZOD impact strength was measured by an impact strength tester. The results are shown in Table 4.

[0471] (Extrusion Processability)

[0472] In Examples 3 to 7 and Comparative Examples 2 to 3, when the hinges leaving the twin-screw extruder were pelletized using a pelletizer (water-cooled pelletizer KM-150N manufactured by Katsuya Seisakusho Co., Ltd.), the case where pellets were obtained was recorded as "A", and the case where pellets could not be obtained due to poor cutting of the hinges was recorded as "C". The results are shown in Table 9.

[0473] [Table 4]

[0474] .

[0475] [Table 5]

[0476] .

[0477] [Table 6]

[0478] .

[0479] [Table 7]

[0480] .

[0481] [Table 8]

[0482] .

[0483] [Table 9]

[0484] .

[0485] As shown in Table 4, in the molded articles using the resin compositions of Examples 1 to 10, a core-shell structure was formed, and the loss coefficient values ​​at 20° C. and 40° C. were greater than those of Comparative Examples 1 and 2 and Reference Example 1.

[0486] Furthermore, it was found that the molded articles using the resin compositions of Examples 1 to 10 were superior in appearance, smaller in volume average dispersion diameter, and larger in IZOD impact strength than those of Comparative Example 1.

[0487] In contrast, it can be seen that in the molded articles using the resin compositions of Comparative Examples 1, 2, and Reference Example 1, a core-shell structure is not formed, the loss coefficient value at 20°C is smaller than that of Examples 1 to 10, and the loss coefficient value at 40°C is also less than that of Examples 1 to 10. In addition, it can be seen that the appearance of the molded article of Comparative Example 1 is inferior to that of Examples 1 to 10, the volume average dispersion diameter is large, and the IZOD impact strength is small. That is, it can be seen that the dispersibility of the thermoplastic resin (A) in the polar resin (C) of Comparative Examples 1 and 2 is worse than that of Examples 1 to 10.

[0488] According to Table 5, it can be seen that in the molded articles using the resin compositions of Examples 11 to 17, a core-shell structure is formed, and the values ​​of the loss coefficients at 20° C. and 40° C. are higher than those of Comparative Example 3 and Reference Example 2.

[0489] Furthermore, it was found that the molded articles using the resin compositions of Examples 11 to 17 had excellent appearance and smaller volume average dispersion diameter than those of Comparative Example 3.

[0490] In contrast, it can be seen that in the molded article using the resin composition of Comparative Example 3, a core-shell structure is not formed, and the values ​​of the loss coefficient at 20°C and 40°C are less than those of Examples 11 to 17. In addition, it can be seen that the appearance of the molded article of Comparative Example 3 is inferior to that of Examples 11 to 17, and the volume average dispersion diameter is larger. That is, it can be seen that the dispersibility of the thermoplastic resin (A) in the polar resin (C) of Comparative Example 3 is worse than that of Examples 11 to 17.

[0491] According to Table 6, in the molded articles using the resin compositions of Examples 18 and 19, a core-shell structure is formed, and the values ​​of the loss coefficients at 0°C, 20°C and 40°C are equal to or higher than those of Comparative Example 4 and Reference Example 3.

[0492] Furthermore, it was found that the molded articles using the resin compositions of Examples 18 and 19 had better appearance and smaller volume average dispersion diameter than that of Comparative Example 4.

[0493] In contrast, it can be seen that the core-shell structure is not formed in the molded articles using the resin compositions of Comparative Example 4 and Reference Example 3, and the values ​​of the loss coefficients at 0°C, 20°C, and 40°C are smaller than those of Examples 18 and 19. In addition, it can be seen that the appearance of the molded article of Comparative Example 4 is inferior and the volume average dispersion diameter is larger than those of Examples 18 and 19. That is, it can be seen that the dispersibility of the thermoplastic resin (A) in the polar resin (C) of Comparative Example 4 is worse than that of Examples 18 and 19.

[0494] According to Table 7, it can be seen that in the molded articles using the resin compositions of Examples 20 to 23, a core-shell structure is formed, the loss coefficient value at 0 to 40°C is greater than the loss coefficient value at the corresponding temperature of Reference Example 4, and the loss coefficient value at 10 to 30°C becomes particularly large.

[0495] Furthermore, it was found that the molded articles using the resin compositions of Examples 20 to 23 all had excellent appearance and small volume average dispersion diameter.

[0496] According to Table 8, it can be seen that a core-shell structure is formed in the molded products using the resin compositions of Examples 24 to 29, and the values ​​of the loss coefficients at 20 to 100°C are greater than the values ​​of the loss coefficients at the corresponding temperatures of Reference Example 5. In addition, the values ​​of the loss coefficients at 20 to 100°C of Examples 26 and 27 are equivalent to the loss coefficients at the corresponding temperatures of Comparative Example 5.

[0497] Furthermore, it was found that the molded articles using the resin compositions of Examples 24 to 29 were superior in appearance and had smaller volume average dispersion diameters than those of Comparative Example 5.

[0498] In contrast, it can be seen that the core-shell structure is not formed in the molded article using the resin composition of Comparative Example 5, and the appearance of the molded article is poor and the volume average dispersion diameter is large compared with Examples 24 to 29. That is, it can be seen that the dispersibility of the thermoplastic resin (A) in the polar resin (C) of Comparative Example 5 is worse than that of Examples 24 to 29.

[0499] According to Table 9, it can be seen that when the resin compositions of Examples 30 to 32 containing modified resin-3 or modified resin-4 are used, extrusion processability is good, and a core-shell structure is formed in the molded articles obtained by these resin compositions. In addition, it can be seen that the loss coefficient is improved in a wide temperature range of 0 to 80° C. compared with Reference Example 6 containing a PPS resin monomer.

[0500] On the other hand, it was found that the resin composition of Comparative Example 6 not containing a modified resin had low compatibility with the polar resin, so pellets could not be obtained and the loss coefficient could not be measured.

[0501] Industrial Applicability

[0502] The resin composition of the present invention is a resin composition that shows high shock absorbing properties even at relatively high temperatures, has good moldability, and is excellent in impact resistance. Therefore, the molded products thereof can be used for pellets, veils, shock absorbing materials, sound insulating materials, compatibilizers, sole materials, floor materials, adhesives, binders, laminates, fibers, and automobile parts.

[0503] Description of Reference Numerals

[0504] 10, 11: Core-shell structure

[0505] 10a: Nuclear

[0506] 10b, 11b: Shell

[0507] 11a, 11c: Domain area

[0508] 20: Matrix.

Claims

1. A resin composition comprising a thermoplastic resin (A), a thermoplastic resin (B), and a polar resin (C), The thermoplastic resin (A) is a block copolymer having a block (A-1) containing more than 70 mol% of an aromatic vinyl compound unit and a block (A-2) containing 30 mol% or more of a conjugated diene unit, or a hydrogenated product thereof, The thermoplastic resin (B) is a block copolymer having a polymer block (B-1) derived from an aromatic vinyl compound and a polymer block (B-2) derived from a conjugated diene compound, or a hydrogenated product thereof, modified with a compound having a reactive functional group, or a modified olefin resin modified with a compound having a reactive functional group. The resin composition satisfies the following conditions (1) to (3), (1) The thermoplastic resin (B) has a reactive functional group; (2) The thermoplastic resin (A) and the thermoplastic resin (B) are different types of resins; (3) With respect to the total mass of the resin composition, the content of the thermoplastic resin (A) is 1 to 30 mass %, the content of the thermoplastic resin (B) is 1 to 30 mass %, and the content of the polar resin (C) is 40 to 98 mass %, respectively; The molded article of the resin composition has a core-shell structure, in which the thermoplastic resin (A) and the thermoplastic resin (B) are dispersed in the polar resin (C), and the dispersion diameter D(A) of the thermoplastic resin (A) and the dispersion diameter D(B) of the thermoplastic resin (B) satisfy the relationship of D(A)<D(B), The thermoplastic resin (A) has a structure represented by the following formula (X) or a structure of a hydrogenated product thereof, In the above formula (X), R 1 ~R 3 Each independently represents a hydrogen atom or a hydrocarbon group having 1 to 11 carbon atoms, and a plurality of R 1 ~R 3 They can be the same or different. The thermoplastic resin (B) has one or more functional groups selected from the group consisting of an alkoxysilyl group, a carboxyl group, an amino group, a hydroxyl group, an epoxy group, a group derived from an acid anhydride, an ester group, and an oxazoline group.

2. The resin composition according to claim 1, wherein The thermoplastic resin (A) is a block copolymer having a block (A-1) containing more than 80 mol % of an aromatic vinyl compound unit and a block (A-2) containing 50 mol % or more of a conjugated diene unit, or a hydrogenated product thereof.

3. The resin composition according to claim 1 or 2, wherein The thermoplastic resin (A) is a hydrogenated product of a block copolymer having a polymer block (A-1) containing more than 70 mol% of an aromatic vinyl compound unit and a polymer block (A-2) containing 30 mol% or more of a conjugated diene unit, the hydrogenation rate of the hydrogenated product being 50 to 99 mol%.

4. The resin composition according to claim 1 or 2, wherein The glass transition temperature of the thermoplastic resin (A) is within the range of -30 to +50°C.

5. The resin composition according to claim 1 or 2, wherein The thermoplastic resin (A) does not have an alkoxysilyl group, a carboxyl group, an amino group, a hydroxyl group, an epoxy group, a group derived from an acid anhydride, an ester group, a mercapto group, and an oxazoline group.

6. The resin composition according to claim 1 or 2, wherein The thermoplastic resin (B) is an epoxy group-containing resin.

7. The resin composition according to claim 1 or 2, wherein The thermoplastic resin (B) has, as the reactive functional group, a group derived from at least one selected from maleic anhydride and an alkoxysilyl group.

8. The resin composition according to claim 1 or 2, wherein The thermoplastic resin (B) is a block copolymer having a polymer block (B-1) containing more than 70 mol% of an aromatic vinyl compound unit and a polymer block (B-2) containing 30 mol% or more of a conjugated diene unit, or a hydrogenated product thereof, modified with a compound having the aforementioned reactive functional group, or a modified product obtained by modifying an olefin-based resin with a compound having the aforementioned reactive functional group.

9. The resin composition according to claim 1, wherein The core-shell structure includes a core-shell structure including a plurality of regions distributed in an island shape, wherein the plurality of regions include at least one of a region of the thermoplastic resin (A) and a region of the polar resin (C).

10. The resin composition according to claim 1 or 2, wherein At least one of the glass transition temperature and the melting point of the polar resin (C) is 80° C. or higher.

11. The resin composition according to claim 1 or 2, wherein The polar resin (C) is at least one selected from the group consisting of polyamide resins, polyester resins, polyacetal resins, polyphenylene sulfide resins, polyurethane resins, polyvinyl alcohol resins, and polycarbonate resins. 12 . An automobile member comprising the resin composition according to claim 1 .

13. A molded article of a resin composition, the resin composition comprising a thermoplastic resin (A), a thermoplastic resin (B), and a polar resin (C), The thermoplastic resin (A) is a block copolymer having a block (A-1) containing more than 70 mol% of an aromatic vinyl compound unit and a block (A-2) containing 30 mol% or more of a conjugated diene unit, or a hydrogenated product thereof, The thermoplastic resin (B) is a block copolymer having a polymer block (B-1) derived from an aromatic vinyl compound and a polymer block (B-2) derived from a conjugated diene compound, or a hydrogenated product thereof, modified with a compound having a reactive functional group, or a modified olefin resin modified with a compound having a reactive functional group. The resin composition satisfies the following conditions (1) to (3), In the above molded article, there is a core-shell structure, in which the thermoplastic resin (A) and the thermoplastic resin (B) are dispersed in the polar resin (C), and the dispersion diameter D(A) of the thermoplastic resin (A) and the dispersion diameter D(B) of the thermoplastic resin (B) satisfy the relationship of D(A)<D(B), (1) The thermoplastic resin (B) has a reactive functional group; (2) The thermoplastic resin (A) and the thermoplastic resin (B) are different types of resins; (3) With respect to the total mass of the resin composition, the content of the thermoplastic resin (A) is 1 to 30 mass %, the content of the thermoplastic resin (B) is 1 to 30 mass %, and the content of the polar resin (C) is 40 to 98 mass %, respectively; The thermoplastic resin (A) has a structure represented by the following formula (X) or a structure of a hydrogenated product thereof, In the above formula (X), R 1 ~R 3 Each independently represents a hydrogen atom or a hydrocarbon group having 1 to 11 carbon atoms, and a plurality of R 1 ~R 3 They can be the same or different. The thermoplastic resin (B) has one or more functional groups selected from the group consisting of an alkoxysilyl group, a carboxyl group, an amino group, a hydroxyl group, an epoxy group, a group derived from an acid anhydride, an ester group, and an oxazoline group.

14. The method for producing a resin composition according to any one of claims 1 to 11, wherein A mixture of a thermoplastic resin (A) and a thermoplastic resin (B) in a molten state is prepared, and the mixture is mixed with a polar resin (C).

15. The method for producing a resin composition according to claim 14, comprising: A step of adding a free radical initiator in a molten state to a mixture of a thermoplastic resin (A) and a precursor (B0) of a thermoplastic resin (B) satisfying the following conditions (4) and (5), thereby introducing a reactive functional group into the precursor (B0) to obtain the thermoplastic resin (A) and the thermoplastic resin (B) having a reactive functional group, (4) The thermoplastic resin (A) is a block copolymer having a block (A-1) containing more than 70 mol% of an aromatic vinyl compound unit and a block (A-2) containing more than 30 mol% of a conjugated diene unit, or a hydrogenated product thereof, and has a glass transition temperature in the range of -30 to +50°C, (5) The glass transition temperature of the precursor (B0) of the thermoplastic resin (B) is within the range of -100 to -31°C.

16. The method for producing a resin composition according to claim 15, wherein The thermoplastic resin (A) is a hydrogenated product of a block copolymer having a block (A-1) and a block (A-2), and the hydrogenation rate of the hydrogenated product is 50 to 99 mol%.

17. The method for producing a resin composition according to claim 14, wherein The reactive functional group of the thermoplastic resin (B) is one or more functional groups selected from the group consisting of an alkoxysilyl group, an epoxy group, and a group derived from an acid anhydride.

18. A method for producing a resin modifier comprising a thermoplastic resin (A) and a thermoplastic resin (B), comprising: A step of adding a free radical initiator in a molten state to a mixture of a thermoplastic resin (A) and a precursor (B0) of a thermoplastic resin (B) satisfying the following conditions (4) and (5), thereby introducing a reactive functional group into the precursor (B0) to obtain the thermoplastic resin (A) and the thermoplastic resin (B) having a reactive functional group, (4) The thermoplastic resin (A) is a block copolymer having a block (A-1) containing more than 70 mol% of an aromatic vinyl compound unit and a block (A-2) containing more than 30 mol% of a conjugated diene unit, or a hydrogenated product thereof, and has a glass transition temperature in the range of -30 to +50°C, (5) the glass transition temperature of the precursor (B0) of the thermoplastic resin (B) is within the range of -100 to -31°C, The thermoplastic resin (B) is a block copolymer having a polymer block (B-1) derived from an aromatic vinyl compound and a polymer block (B-2) derived from a conjugated diene compound, or a hydrogenated product thereof, modified with a compound having a reactive functional group, or a modified olefin resin modified with a compound having a reactive functional group. The thermoplastic resin (A) has a structure represented by the following formula (X) or a structure of a hydrogenated product thereof, In the above formula (X), R 1 ~R 3 Each independently represents a hydrogen atom or a hydrocarbon group having 1 to 11 carbon atoms, and a plurality of R 1 ~R 3 They can be the same or different. The thermoplastic resin (B) has one or more functional groups selected from the group consisting of an alkoxysilyl group, a carboxyl group, an amino group, a hydroxyl group, an epoxy group, a group derived from an acid anhydride, an ester group, and an oxazoline group.

Citation Information

Patent Citations

  • Production of ethylene copolymer

    JP1986127709A

  • Block copolymer, composition containing the same, and vibration damper

    JP2002284830A

  • Hydrogenated copolymer and its composition

    JP2006117879A

  • Hydrogenated block copolymer and composition thereof

    JP2010053319A

  • Modified copolymer and rubber composition and pneumatic tire using the same

    JP2011132298A